Electrode composition, electrode sheet for all-solid-state secondary battery, and all-solid-state secondary battery, and method for manufacturing the electrode composition, electrode sheet for all-solid-state secondary battery, and all-solid-state secondary battery.
Patent Information
- Application Number
- JP2023551568
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-09-14
- Filing Date
- 2022-09-28
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2042-09-28
AI Technical Summary
【0009】 本発明は、含有量の低減を可能としながらも固体粒子の優れた分散特性及び強固な結着性を実現する電極組成物を提供できる。また、本発明は、この電極組成物で構成した活物質層を有する、全固体二次電池用電極シート及び全固体二次電池を提供できる。更に、本発明は、電極組成物、全固体二次電池用電極シート及び全固体二次電池の各製造方法を提供できる。
Smart Images

Figure 0007933778000019 
Figure 0007933778000001 
Figure 0007933778000002
Abstract
Description
[Technical Field]
[0001] The present invention relates to an electrode composition, an electrode sheet for an all-solid-state secondary battery, and an all-solid-state secondary battery, as well as to a method for manufacturing the electrode composition, the electrode sheet for an all-solid-state secondary battery, and the all-solid-state secondary battery. [Background technology]
[0002] All-solid-state rechargeable batteries consist entirely of solid negative electrodes, electrolytes, and positive electrodes, significantly improving the safety and reliability issues associated with batteries using organic electrolytes. They are also expected to offer longer lifespans. Furthermore, all-solid-state rechargeable batteries can be constructed with electrodes and electrolytes directly arranged in series. Therefore, they enable higher energy density compared to rechargeable batteries using organic electrolytes, and are expected to have applications in electric vehicles and large-scale storage batteries.
[0003] In such all-solid-state secondary batteries, materials that form the active material layer (also called the electrode layer) include inorganic solid electrolytes and active materials. These inorganic solid electrolytes, in particular oxide-based inorganic solid electrolytes and sulfide-based inorganic solid electrolytes, are expected to be electrolyte materials with high ionic conductivity approaching that of organic electrolytes. As materials for forming the active material layer of an all-solid-state secondary battery (also called active material layer forming material or electrode composition), materials (e.g., slurry compositions) have been proposed in which the above-mentioned inorganic solid electrolyte, active material, and binder (binding agent) are dispersed or dissolved in a dispersion medium, and among these, materials using two types of binders in combination have also been proposed. For example, Patent Document 1 describes a composite material comprising a solid electrolyte, an active material, a nonpolar solvent, a first binder insoluble in the nonpolar solvent, and a second binder soluble in the nonpolar solvent, wherein the SP values of the first binder and the second binder are different. [Prior art documents] [Patent Documents]
[0004] [Patent Document 1] Japanese Patent Publication No. 2015-244428 [Overview of the project] [Problems that the invention aims to solve]
[0005] When forming an active material layer using solid particulate materials (inorganic solid electrolytes, active materials, conductive additives, etc.), various properties are required of the active material layer forming material and the binder used therein from the viewpoint of improving the battery performance of all-solid-state secondary batteries (for example, reducing battery resistance, improving rate characteristics or cycle characteristics). For example, the active material layer forming material is required to have excellent dispersion stability (initial dispersibility and dispersion stability are collectively called dispersion characteristics) that stably maintains the good initial dispersibility of the solid particulate material (also called solid particles) immediately after preparation. Furthermore, the active material layer formed with the active material layer forming material is required to have binding properties (adhesion) that firmly bind (adhere) the solid particles. On the other hand, since binders have poor ionic conductivity and electronic conductivity, it is required to reduce the content of the active material layer forming material and the active material layer from the viewpoint of suppressing an increase in battery resistance. As described above, active material layer-forming materials are required to achieve both conflicting properties: reducing the binder content while simultaneously achieving good dispersion characteristics of solid particles and strong bonding properties.
[0006] The present invention aims to provide an electrode composition that enables a reduction in the polymer binder content while achieving excellent dispersion characteristics and strong binding properties of solid particles. Furthermore, the present invention aims to provide an electrode sheet for an all-solid-state secondary battery and an all-solid-state secondary battery using this electrode composition, as well as a method for manufacturing the electrode composition, the electrode sheet for an all-solid-state secondary battery, and the all-solid-state secondary battery. [Means for solving the problem]
[0007] In conventional active material forming materials, even with improvements such as changing the mixing order, the group of solid particles containing inorganic solid electrolytics, active materials, etc., was assumed to be a uniform mixture, and a binder was selected to disperse and bind these solid particles as a whole. However, after diligently studying active material layer-forming materials, the inventors concluded that, generally, increasing the interaction of a binder with an inorganic solid electrolyte also increases its interaction with the active material. Therefore, even when considering a binder to be used in conjunction with a solid particle group that includes an inorganic solid electrolyte and an active material as a single mixture, it was concluded that this was insufficient to achieve both the dispersion characteristics and binding properties of the solid particle group and the reduction of the binder content. Thus, after further investigation, the inventors conceived the idea of improving the binder for each solid particle group by considering the inorganic solid electrolyte and the active material as separate solid particle groups, rather than treating them as a single mixture, in an active material layer-forming material containing an active material, an inorganic solid electrolyte, and a dispersion medium. Based on this idea, the inventors have found that by using a combination of binders that preferentially adsorb to the active material and a binder that preferentially adsorbs to the inorganic solid electrolytic, among the binders dissolved in the dispersion medium, it is possible to reduce the total binder content while stably dispersing the active material and inorganic solid electrolytic in the active material layer forming material not only immediately after preparation but also over time (excellent dispersion characteristics), and forming an active material layer in which the active material and inorganic solid electrolyte are firmly bound together. Furthermore, the inventors have found that this active material layer forming material can realize a low-resistance active material layer in which solid particles are firmly bound together, and that an all-solid-state secondary battery incorporating this active material layer can achieve low resistance and excellent battery performance. This invention was completed after further consideration based on these findings.
[0008] In other words, the above problems were solved by the following means. <1> An electrode composition comprising an inorganic solid electrolyte having conductivity of metal ions belonging to Group 1 or Group 2 of the periodic table, an active material, a polymer binder, and a dispersion medium, Polymer binder, A polymer binder A that dissolves in a dispersion medium, wherein the adsorption rate to the active material in the dispersion medium is 20% or more, and is greater than the adsorption rate to the inorganic solid electrolyte, A polymer binder that dissolves in a dispersion medium, wherein polymer binder B has an adsorption rate of 20% or more to an inorganic solid electrolyte in the dispersion medium, and is greater than the adsorption rate to the active material, and An electrode composition containing the following: <2> Contains a conductive additive, <1> The electrode composition described above. <3> The polymer forming at least one of polymer binder A and polymer binder B includes a component having a functional group selected from the following functional group (a). <1> or <2> The electrode composition described above. <Functional group group (a)> Hydroxyl group, amino group, carboxyl group, sulfo group, phosphate group, phosphonic acid group, sulfanyl group, ether bond, imino group, amide bond, imide bond, urethane bond, urea bond, heterocyclic group, aryl group, carboxylic anhydride group <4> The polymer forming polymer binder A has at least one of the following types of bonds in its main chain: urethane bond, urea bond, amide bond, imide bond, and ester bond. <1> ~ <3> An electrode composition as described in any one of the following. <5> The polymer forming polymer binder B is obtained by polymerizing monomers having carbon-carbon unsaturated bonds. <1> ~ <4> An electrode composition as described in any one of the following. <6> The polymer binder A content is 1.5% by mass or less of the solid content of the electrode composition by 100% by mass. The polymer binder B content is 1.5% by mass or less of the solid content of the electrode composition by 100% by mass. <1> ~ <5> An electrode composition as described in any one of the following. <7> the above <1> ~ <6> An electrode sheet for an all-solid-state secondary battery having an active material layer formed using any one of the electrode compositions described in the preceding paragraph. <8> An all-solid-state secondary battery comprising a positive electrode active material layer, a solid electrolyte layer, and a negative electrode active material layer in this order, At least one of the positive electrode active material layer and the negative electrode active material layer <1> ~ <6> An all-solid-state secondary battery having an active material layer formed using an electrode composition described in any one of the above. <9> the above <1> ~ <6> A method for producing an electrode composition according to any of the following: A step of preparing an active material composition containing an active material, a polymer binder A, and a dispersion medium, A step of preparing a solid electrolyte composition containing an inorganic solid electrolyte, a polymer binder B, and a dispersion medium, A step of mixing the active material composition and the solid electrolyte composition, A method for producing an electrode composition having the following characteristics. <10> the above <1> ~ <6> A method for manufacturing an electrode sheet for an all-solid-state secondary battery, comprising forming a film of the electrode composition described in any one of the above. <11> the above <10> A method for manufacturing an all-solid-state secondary battery, comprising manufacturing an all-solid-state secondary battery via the manufacturing method described above. [Effects of the Invention]
[0009] The present invention provides an electrode composition that achieves excellent dispersion characteristics and strong binding properties of solid particles while enabling a reduction in content. Furthermore, the present invention provides an electrode sheet for an all-solid-state secondary battery and an all-solid-state secondary battery having an active material layer composed of this electrode composition. Moreover, the present invention provides methods for manufacturing the electrode composition, the electrode sheet for an all-solid-state secondary battery, and the all-solid-state secondary battery. [Brief explanation of the drawing]
[0010] [Figure 1] This is a schematic longitudinal cross-sectional view showing an all-solid-state secondary battery according to a preferred embodiment of the present invention. [Modes for carrying out the invention]
[0011] In this invention, a numerical range represented using "~" means a range that includes the values written before and after "~" as the lower and upper limits. In this invention, when multiple numerical ranges are set and explained for the content of components, physical properties, etc., the upper and lower limits that form the numerical range are not limited to the specific combination of upper and lower limits written before and after "~" as a specific numerical range, but can be a numerical range formed by appropriately combining the upper and lower limits of each numerical range. In this invention, the designation of a compound (for example, when referring to it with "compound" at the end) includes not only the compound itself, but also its salts and ions. It also includes derivatives in which parts have been altered, such as by introducing substituents, to the extent that the effects of this invention are not impaired. In this invention, (meth)acrylic means either or both acrylic and methacrylic. The same applies to (meth)acrylate. In the present invention, substituents, linking groups, etc. (hereinafter referred to as substituents, etc.) that are not explicitly stated as substituted or unsubstituted may have appropriate substituents. Therefore, even when simply referred to as a YYY group in the present invention, this YYY group includes not only the unsubstituted form but also the form with substituents. The same applies to compounds that are not explicitly stated as substituted or unsubstituted. A preferred substituent is, for example, substituent Z, which will be described later. In the present invention, when there are multiple substituents indicated by specific symbols, or when multiple substituents are specified simultaneously or alternatively, it means that each substituent may be the same as or different from the others. Furthermore, even if not specifically stated otherwise, when multiple substituents are adjacent to each other, they may be linked to each other or fused to form a ring. In this invention, "polymer" means a polymer and is synonymous with so-called high-molecular-weight compounds. Furthermore, "polymer binder" (also simply called "binder") means a binder composed of polymers and includes both the polymer itself and binders composed (formed) containing polymers.
[0012] In the present invention, a composition containing an inorganic solid electrolyte, an active material, and a dispersion medium, and used as a material for forming the active material layer of an all-solid-state secondary battery (active material layer forming material), is referred to as an electrode composition for an all-solid-state secondary battery, or simply an electrode composition. On the other hand, a composition containing an inorganic solid electrolyte and used as a material for forming the solid electrolyte layer of an all-solid-state secondary battery is referred to as an inorganic solid electrolyte-containing composition, and this composition usually does not contain an active material. In the present invention, the electrode composition includes a positive electrode composition containing a positive electrode active material and a negative electrode composition containing a negative electrode active material. Therefore, either or both of the positive electrode composition and the negative electrode composition may be simply referred to as the electrode composition, and either or both of the positive electrode active material layer and the negative electrode active material layer may be simply referred to as the active material layer or electrode active material layer. Furthermore, either or both of the positive electrode active material and the negative electrode active material may be simply referred to as the active material or electrode active material.
[0013] [Electrode composition] The electrode composition of the present invention contains an inorganic solid electrolyte (SE) having conductivity of metal ions belonging to Group 1 or Group 2 of the periodic table, an active material (AC), a polymer binder (PB), and a dispersion medium (D). The polymer binder (PB) contains polymer binder A, which dissolves in the dispersion medium (D) and satisfies the following adsorption rate, and polymer binder B, which dissolves in the dispersion medium (D) and satisfies the following adsorption rate. Polymer binder A and polymer binder B may each be present in the electrode composition as one type, or two or more types may be present. Polymer binder A: Has an adsorption rate of 20% or more for the active material (AC) in the dispersion medium (D), and is greater than the adsorption rate for the inorganic solid electrolyte (SE). Polymer binder B: Has an adsorption rate of 20% or more to the inorganic solid electrolyte (SE) in the dispersion medium (D), and is greater than the adsorption rate to the active material (AC).
[0014] In the dispersion medium (D), the electrode composition of the present invention, which contains a combination of polymer binder A and polymer binder B as polymer binders (PB) for inorganic solid electrolyte (SE) and active material (AC), can stably disperse the inorganic solid electrolyte (SE) and active material (AC) not only immediately after preparation but also over time, even when the total content of polymer binders (especially the combined content of polymer binders A and B) is reduced (excellent dispersion characteristics). Furthermore, the inorganic solid electrolyte (SE) and active material (AC) can be firmly bonded together during film formation of the electrode composition. Therefore, by using this electrode composition as an active material layer forming material, it is possible to realize a low-resistance active material layer in which the inorganic solid electrolyte (SE) and active material (AC) are firmly bonded, and furthermore, an all-solid-state secondary battery exhibiting low resistance and excellent battery characteristics.
[0015] The exact reasons are not yet clear, but they can be considered as follows: The electrode composition of the present invention contains polymer binder A, which exhibits higher adsorption (preferential adsorption) to the active material (AC) than to the inorganic solid electrolyte (SE), and polymer binder B, which exhibits higher adsorption (preferential adsorption) to the inorganic solid electrolyte (SE) than to the active material (AC). In this electrode composition, the preferential adsorption amount of polymer binders A and B to the active material (AC) or inorganic solid electrolyte (SE) cannot be uniquely determined because it varies depending on the adsorption rate of each binder, the difference in adsorption rates, the content of each component, the type of dispersion medium (D), and the preparation method or conditions of the electrode composition. However, it is presumed that polymer binder A, which exhibits the above-mentioned adsorption rate, is mostly adsorbed onto the active material (AC), and polymer binder B is mostly adsorbed onto the inorganic solid electrolyte (SE). Therefore, polymer binder A can improve the dispersibility of the preferentially adsorbed active material (AC), and polymer binder B can improve the dispersibility of the preferentially adsorbed inorganic solid electrolyte (SE). Furthermore, both polymer binders A and B are thought to dissolve in the dispersion medium (D), expand their molecular chains, and repel each other, thereby effectively suppressing (re)aggregation or precipitation (excellent dispersion characteristics). Moreover, the adsorption and dispersion states between the polymer binders and the active material (AC) or inorganic solid electrolyte (SE) are maintained even during film formation of the electrode composition. As a result, the active material (AC) or inorganic solid electrolyte (SE) is thought to be firmly bound in the formed active material layer while maintaining a high degree of dispersion. Moreover, by using polymer binders A and B in combination, the active material (AC) and inorganic solid electrolyte (SE) can be adsorbed separately, dispersed, and bound, thus reducing the amount of polymer binder required to disperse and bind the active material (AC) and inorganic solid electrolyte (SE). Therefore, the inhibition of ion conduction path and electron conduction path construction by polymer binder (PB) can be suppressed. Furthermore, since the active material layer can be formed while maintaining the above-mentioned highly dispersed state, it is thought that the inorganic solid electrolyte (SE) and active material (AC) are less likely to be unevenly distributed, thereby suppressing variations in the contact state within the active material layer.
[0016] Thus, by forming an active material layer using an electrode composition that enables a reduction in polymer binder content while achieving excellent dispersion characteristics and strong bonding of inorganic solid electrolyte (SE) and active material (AC), it is possible to form an active material layer in which the inorganic solid electrolyte (SE) and active material (AC) are firmly bonded together while ensuring direct contact and suppressing uneven distribution of the inorganic solid electrolyte (SE) and active material (AC). Therefore, it is expected that an all-solid-state secondary battery incorporating this active material layer will exhibit low resistance (high ionic conductivity and high electronic conductivity) and excellent battery characteristics such as rate characteristics.
[0017] Polymer binders A and B are thought to function in the electrode composition by dissolving in the dispersion medium (D), adsorbing onto the active material (AC) or inorganic solid electrolyte (SE), or interposing between solid particles, thereby dispersing the active material (AC) or inorganic solid electrolyte (SE) in the dispersion medium (D). On the other hand, polymer binders A and B are thought to function as binders in the active material layer by adsorbing onto the active material (AC) or inorganic solid electrolyte (SE) and binding them together. Polymer binders A and B preferentially adsorb onto the active material (AC) or inorganic solid electrolyte (SE), respectively, but may also adsorb onto the inorganic solid electrolyte (SE) or active material (AC). Here, the adsorption of polymer binders A and B onto the active material (AC) or inorganic solid electrolyte (SE) is not particularly limited, but includes not only physical adsorption but also chemical adsorption (adsorption by chemical bond formation, adsorption by electron transfer, etc.). Furthermore, polymer binders A and B can also function as binders that bind the current collector to the solid particles.
[0018] Such electrode compositions exhibit the excellent properties described above and can therefore be preferably used as electrode sheets for all-solid-state secondary batteries and as materials for forming the active material layer (structural layer forming material) of all-solid-state secondary batteries. In particular, they can be preferably used as materials for forming the positive electrode active material layer.
[0019] The electrode composition of the present invention is preferably a slurry in which an inorganic solid electrolyte and an active material are dispersed in a dispersion medium. The electrode composition of the present invention is preferably a non-aqueous composition. In the present invention, a non-aqueous composition includes not only a form that does not contain water, but also a form in which the water content (also called water content) is preferably 500 ppm or less. In a non-aqueous composition, the water content is more preferably 200 ppm or less, even more preferably 100 ppm or less, and particularly preferably 50 ppm or less. When the electrode composition is a non-aqueous composition, the deterioration of the inorganic solid electrolyte can be suppressed. The water content refers to the amount of water contained in the electrode composition (mass ratio to the electrode composition), and specifically, it is the value measured by filtering through a 0.02 μm membrane filter and using Karl Fischer titration.
[0020] The following describes the components contained in and potentially contained in the electrode composition of the present invention.
[0021] <Inorganic solid electrolyte (SE)> The electrode composition of the present invention contains an inorganic solid electrolyte (SE). In this invention, an inorganic solid electrolyte refers to an inorganic solid electrolyte, and a solid electrolyte is a solid electrolyte that can move ions within itself. Since it does not contain organic materials as the main ion-conducting material, it is clearly distinguished from organic solid electrolytes (polymer electrolytes such as polyethylene oxide (PEO), and organic electrolyte salts such as lithium bis(trifluoromethanesulfonyl)imide (LiTFSI)). Furthermore, since inorganic solid electrolytes are solid in a steady state, they do not usually dissociate or become liberated into cations and anions. In this respect, they are clearly distinguished from inorganic electrolyte salts (LiPF6, LiBF4, lithium bis(fluorosulfonyl)imide (LiFSI), LiCl, etc.) that dissociate or become liberated into cations and anions in the electrolyte or polymer. Inorganic solid electrolytes are not particularly limited as long as they have conductivity of metal ions belonging to Group 1 or Group 2 of the periodic table, and generally, they do not have electronic conductivity.
[0022] The inorganic solid electrolyte contained in the electrode composition of the present invention can be appropriately selected from solid electrolyte materials commonly used in all-solid-state secondary batteries. For example, examples of inorganic solid electrolytes include (i) sulfide-based inorganic solid electrolytes, (ii) oxide-based inorganic solid electrolytes, (iii) halide-based inorganic solid electrolytes, and (iv) hydride-based inorganic solid electrolytes. From the viewpoint of forming a better interface between the active material and the inorganic solid electrolyte, sulfide-based inorganic solid electrolytes are preferred. In the case of a lithium-ion battery in the all-solid-state secondary battery of the present invention, it is preferable that the inorganic solid electrolyte has ionic conductivity for lithium ions.
[0023] (i) Sulfide-based inorganic solid electrolyte The sulfide-based inorganic solid electrolyte is preferably one that contains sulfur atoms, has ionic conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, and is also an electronic insulator. The sulfide-based inorganic solid electrolyte is preferably one that contains at least Li, S, and P as elements and has lithium ion conductivity, but may contain other elements other than Li, S, and P as appropriate.
[0024] Examples of sulfide-based inorganic solid electrolytes include lithium-ion conductive inorganic solid electrolytes that satisfy the composition shown in the following formula (S1). L a1 M b1 P c1 S d1 A e1 (S1) In formula (S1), L represents an element selected from Li, Na, and K, with Li being preferred. M represents an element selected from B, Zn, Sn, Si, Cu, Ga, Sb, Al, and Ge. A represents an element selected from I, Br, Cl, and F. a1 to e1 represent the composition ratio of each element, where a1:b1:c1:d1:e1 satisfies 1 to 12:0 to 5:1:2 to 12:0 to 10. a1 is preferably 1 to 9, more preferably 1.5 to 7.5. b1 is preferably 0 to 3, more preferably 0 to 1. d1 is preferably 2.5 to 10, more preferably 3.0 to 8.5. e1 is preferably 0 to 5, more preferably 0 to 3.
[0025] The composition ratio of each element can be controlled by adjusting the amount of raw material compounds used when producing sulfide-based inorganic solid electrolytes, as shown below.
[0026] The sulfide-based inorganic solid electrolyte may be amorphous (glass) or crystalline (glass-ceramic), or partially crystalline. For example, a Li-PS glass containing Li, P, and S, or a Li-PS glass-ceramic containing Li, P, and S can be used. Sulfide-based inorganic solid electrolytes can be produced by the reaction of at least two raw materials from among lithium sulfide (Li2S), phosphorus sulfide (e.g., diphosphorus pentasulfide (P2S5)), elemental phosphorus, elemental sulfur, sodium sulfide, hydrogen sulfide, lithium halides (e.g., LiI, LiBr, LiCl), and sulfides of the element represented by M above (e.g., SiS2, SnS, GeS2).
[0027] In Li-PS-based glass and Li-PS-based glass ceramics, the ratio of Li2S to P2S5 is preferably 60:40 to 90:10, more preferably 68:32 to 78:22, in terms of the molar ratio of Li2S:P2S5. By setting the ratio of Li2S to P2S5 within this range, the lithium ion conductivity can be increased. Specifically, the lithium ion conductivity is preferably 1 × 10⁻⁶. -4 S / cm or more, more preferably 1 × 10 -3 It can be S / cm or more. There is no particular upper limit, but 1 × 10 -1 It is practical for the rate to be less than or equal to S / cm.
[0028] As specific examples of the sulfide-based inorganic solid electrolyte, examples of raw material combinations are shown below. For example, Li2S-P2S5, Li2S-P2S5-LiCl, Li2S-P2S5-H2S, Li2S-P2S5-H2S-LiCl, Li2S-LiI-P2S5, Li2S-LiI-Li2O-P2S5, Li2S-LiBr-P2S5, Li2S-Li2O-P2S5, Li2S-Li3PO4-P2S5, Li2S-P2S5-P2O5, Li2S-P2S5-SiS2, Li2S-P2S5-SiS2-LiCl, Li2S-P2S5-SnS, Li2S-P2S5-Al2S3, Li2S-GeS2, Li2S-GeS2-ZnS, Li2S-Ga2S3, Li2S-GeS2-Ga2S3, Li2S-GeS2-P2S5, Li2S-GeS2-Sb2S5, Li2S-GeS2-Al2S3, Li2S-SiS2, Li2S-Al2S3, Li2S-SiS2-Al2S3, Li2S-SiS2-P2S5, Li2S-SiS2-P2S5-LiI, Li2S-SiS2-LiI, Li2S-SiS2-Li4SiO4, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li 10 GeP2S 12 and the like. However, the mixing ratio of each raw material is not limited. Examples of the method for synthesizing the sulfide-based inorganic solid electrolyte material using such a raw material composition include an amorphization method. Examples of the amorphization method include a mechanical milling method, a solution method, and a melt quenching method. This is because treatment at normal temperature is possible, and the manufacturing process can be simplified.
[0029] (ii) Oxide-based inorganic solid electrolyte The oxide-based inorganic solid electrolyte preferably contains oxygen atoms, has ion conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, and has electronic insulation properties. The oxide-based inorganic solid electrolyte preferably has an ion conductivity of 1×10 -6 S / cm or more, more preferably 5×10 -6 S / cm or more, and particularly preferably 1×10 -5 S / cm or more. The upper limit is not particularly limited, but is 1×10 -1Practically, it is not more than S / cm.
[0030] Specific examples of the compound include, for example, Li xa La ya TiO₃ [xa satisfies 0.3≦xa≦0.7, ya satisfies 0.3≦ya≦0.7.] (LLT); Li xb La yb Zr zb M bb mb O nb (M bb is one or more elements selected from Al, Mg, Ca, Sr, V, Nb, Ta, Ti, Ge, In and Sn. xb satisfies 5≦xb≦10, yb satisfies 1≦yb≦4, zb satisfies 1≦zb≦4, mb satisfies 0≦mb≦2, and nb satisfies 5≦nb≦20.); Li xc B yc M cc zc O nc (M cc is one or more elements selected from C, S, Al, Si, Ga, Ge, In and Sn. xc satisfies 0<xc≦5, yc satisfies 0<yc≦1, zc satisfies 0<zc≦1, and nc satisfies 0<nc≦6.); Li xd (Al,Ga) yd (Ti,Ge) zd Si ad P md O nd (xd satisfies 1≦xd≦3, yd satisfies 0≦yd≦1, zd satisfies 0≦zd≦2, ad satisfies 0≦ad≦1, md satisfies 1≦md≦7, and nd satisfies 3≦nd≦13.); Li (3-2xe) M ee xe D ee O (xe represents a number of 0 or more and 0.1 or less, M ee represents a divalent metal atom. D ee represents a halogen atom or a combination of two or more halogen atoms.); Li xf Si yf O zf (xf satisfies 1≦xf≦5, yf satisfies 0<yf≦3, zf satisfies 1≦zf≦10.); Lixg S yg O zg (xg satisfies 1≦xg≦3, yg satisfies 0<yg≦2, and zg satisfies 1≦zg≦10.); Li3BO3; Li3BO3-Li2SO4; Li2O-B2O3-P2O5; Li2O-SiO2; Li6BaLa2Ta2O 12 ; Li3PO (4-3 / 2w) N w (w is w<1); Li having a LISICON (Lithium super ionic conductor) type crystal structure 3.5 Zn 0.25 GeO4; La having a perovskite type crystal structure 0.55 Li 0.35 TiO3; LiTi2P3O having a NASICON (Natrium super ionic conductor) type crystal structure 12 ; Li 1+xh+yh (Al,Ga) xh (Ti,Ge) 2-xh Si yh P 3-yh O 12 (xh satisfies 0≦xh≦1, and yh satisfies 0≦yh≦1); Li7La3Zr2O having a garnet type crystal structure 12 (LLZ) and the like. Phosphorus compounds containing Li, P and O are also desirable. For example, lithium phosphate (Li3PO4); LiPON in which part of the oxygen element of lithium phosphate is substituted with nitrogen element; LiPOD 1 (D 1 is preferably one or more elements selected from Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zr, Nb, Mo, Ru, Ag, Ta, W, Pt and Au.) and the like. Furthermore, LiA 1 ON(A 1 is one or more elements selected from Si, B, Ge, Al, C and Ga.) and the like can also be preferably used.
[0031] (iii) Halide-based inorganic solid electrolyte Halide-based inorganic solid electrolytes are preferably compounds that contain halogen atoms, possess conductivity of metal ions belonging to Group 1 or Group 2 of the periodic table, and have electronic insulating properties. The halogenated inorganic solid electrolyte is not particularly limited, but examples include LiCl, LiBr, LiI, and compounds such as Li3YBr6 and Li3YCl6 as described in ADVANCED MATERIALS, 2018, 30, 1803075. Among these, Li3YBr6 and Li3YCl6 are preferred.
[0032] (iv) Hydride-based inorganic solid electrolytes Hydride-based inorganic solid electrolytes are preferably compounds that contain hydrogen atoms, possess ionic conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, and have electronic insulating properties. The hydride-based inorganic solid electrolyte is not particularly limited, but examples include LiBH4, Li4(BH4)3I, and 3LiBH4-LiCl.
[0033] The inorganic solid electrolyte contained in the electrode composition of the present invention is preferably in particulate form within the electrode composition. The shape of the particles is not particularly limited and may be flattened, amorphous, etc., but spherical or granular is preferred. When the inorganic solid electrolyte is in particulate form, the particle size (volume-average particle size) of the inorganic solid electrolyte is not particularly limited, but is preferably 0.01 μm or larger, more preferably 0.1 μm or larger, and even more preferably 0.5 μm or larger. The upper limit is preferably 100 μm or less, more preferably 50 μm or less, and even more preferably 10 μm or less. The particle size of inorganic solid electrolytes is measured using the following procedure: Dilute the inorganic solid electrolyte particles with water (or heptane if the substance is unstable in water) in a 20 mL sample bottle to prepare a 1% by mass dispersion. Irradiate the diluted dispersion sample with 1 kHz ultrasound for 10 minutes and use it for testing immediately thereafter. Using this dispersion sample, acquire data 50 times using a laser diffraction / scattering particle size distribution analyzer LA-920 (product name, manufactured by HORIBA) at a temperature of 25°C with a quartz cell to obtain the volume-average particle size. For other detailed conditions, refer to the Japanese Industrial Standard (JIS) Z 8828:2013 "Particle Size Analysis - Dynamic Light Scattering Method" as needed. Prepare five samples for each level and use their average value.
[0034] The method for adjusting the particle size is not particularly limited, and known methods can be applied, such as using a conventional grinder or classifier. Suitable grinders or classifiers include, for example, mortars, ball mills, sand mills, vibrating ball mills, satellite ball mills, planetary ball mills, swirling airflow jet mills, or sieves. Wet grinding can be performed with a dispersion medium such as water or methanol present during grinding. Classification is preferable to obtain the desired particle size. Classification is not particularly limited and can be performed using sieves, wind classifiers, etc. Classification can be performed both dry and wet.
[0035] The electrode composition may contain one or more types of inorganic solid electrolytes. The content of inorganic solid electrolyte (SE) in the electrode composition is not particularly limited and can be determined as appropriate. For example, in terms of dispersion characteristics and binding properties, the total amount of SE and active material (AC) is preferably 50% by mass or more, more preferably 70% by mass or more, and particularly preferably 90% by mass or more, based on 100% by mass of solid content. As an upper limit, from a similar viewpoint, it is preferably 99.9% by mass or less, more preferably 99.5% by mass or less, and particularly preferably 99% by mass or less. In this invention, solid content (solid components) refers to components that do not volatilize or evaporate when the electrode composition is dried at 150°C for 6 hours under a pressure of 1 mmHg and a nitrogen atmosphere. Typically, it refers to components other than the dispersion medium (D) described later. Furthermore, the content in total solid content refers to the content in 100% by mass of the total mass of solid content.
[0036] In the electrode composition, the ratio of the inorganic solid electrolyte (SE) content to the active material content described later [inorganic solid electrolyte (SE) content:active material content] in 100% by mass of solid content is not particularly limited, but is preferably 1:1 to 1:6, and more preferably 1:1.2 to 1:5.
[0037] <Active material (AC)> The electrode composition of the present invention contains an active material (AC) capable of inserting and releasing ions of metals belonging to Group 1 or Group 2 of the periodic table. The active materials (AC) include positive electrode active materials and negative electrode active materials, which are described below.
[0038] (Cathode active material) The positive electrode active material is an active material capable of inserting and releasing ions of metals belonging to Group 1 or Group 2 of the periodic table, and is preferably capable of reversibly inserting and releasing lithium ions. The material is not particularly limited as long as it has the above characteristics, and may be a transition metal oxide or an element that can be compounded with Li, such as sulfur, by disassembling the battery. In particular, it is preferable to use a transition metal oxide as the positive electrode active material, and the transition metal element M a A transition metal oxide having one or more elements selected from Co, Ni, Fe, Mn, Cu, and V is more preferable. b (Elements from Group 1(Ia), Group 2(IIa), Al, Ga, In, Ge, Sn, Pb, Sb, Bi, Si, P, and B, other than lithium, may be mixed.) a A ratio of 0 to 30 mol% relative to the amount (100 mol%) is preferred. Li / M aA more preferable product is one synthesized by mixing the elements so that their molar ratio is between 0.3 and 2.2. Specific examples of transition metal oxides include (MA) transition metal oxides having a layered rock salt structure, (MB) transition metal oxides having a spinel structure, (MC) lithium-containing transition metal phosphate compounds, (MD) lithium-containing transition metal halogenated phosphate compounds, and (ME) lithium-containing transition metal silicate compounds.
[0039] (MA)Specific examples of transition metal oxides having a layered rock salt structure include LiCoO2 (lithium cobaltate [LCO]), LiNi2O2 (lithium nickelate), and LiNi 0.85 Co 0.10 Al 0.05 O2 (Lithium nickel-cobalt aluminum oxide [NCA]) ), LiLi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (lithium nickel manganese cobalt oxide [NMC]) and LiNi 0.5 Mn 0.5 O2 (lithium manganese nickelate) is one example. (MB)Specific examples of transition metal oxides having a spinel-type structure include LiMn2O4(LMO), LiCoMnO4, Li2FeMn3O8, Li2CuMn3O8, Li2CrMn3O8, and Li2NiMn3O8. Examples of (MC) lithium-containing transition metal phosphate compounds include olivine-type iron phosphates such as LiFePO4 and Li3Fe2(PO4)3, iron pyrophosphates such as LiFeP2O7, cobalt phosphates such as LiCoPO4, and monoclinic vanadium phosphates such as Li3V2(PO4)3 (lithium vanadium phosphate). Examples of (MD) lithium-containing transition metal halide phosphoric acid compounds include iron phosphate fluorides such as Li2FePO4F, manganese phosphate fluorides such as Li2MnPO4F, and cobalt phosphate fluorides such as Li2CoPO4F. Examples of lithium-containing transition metal silicate compounds (ME) include Li2FeSiO4, Li2MnSiO4, and Li2CoSiO4. In the present invention, transition metal oxides having a (MA) layered rock salt type structure are preferred, and LCO or NMC are more preferred.
[0040] The positive electrode active material contained in the electrode composition of the present invention is preferably in particulate form within the electrode composition. The shape of the particles is not particularly limited and may be flattened, amorphous, etc., but spherical or granular is preferred. When the positive electrode active material is in particulate form, the particle size (volume-average particle size) of the positive electrode active material is not particularly limited, but is preferably 0.1 to 50 μm, and more preferably 0.5 to 10 μm. The particle size of the positive electrode active material particles can be adjusted in the same manner as the particle size of the inorganic solid electrolyte, and the measurement method can also be the same as that for the particle size of the inorganic solid electrolyte.
[0041] The positive electrode active material obtained by the calcination method may be used after being washed with water, an acidic aqueous solution, an alkaline aqueous solution, or an organic solvent.
[0042] The electrode composition of the present invention may contain one or more positive electrode active materials. The content of the positive electrode active material in the electrode composition is not particularly limited and can be determined as appropriate. For example, based on 100% by mass of solids, 10 to 97% by mass is preferred, 30 to 95% by mass is more preferred, 40 to 93% by mass is even more preferred, and 50 to 90% by mass is particularly preferred.
[0043] (Negative electrode active material) The negative electrode active material is an active material capable of inserting and releasing ions of metals belonging to Group 1 or Group 2 of the periodic table, and is preferably capable of reversibly inserting and releasing lithium ions. The material is not particularly limited as long as it has the above characteristics, and examples include carbonaceous materials, metal oxides, metal composite oxides, elemental lithium, lithium alloys, and negative electrode active materials that can form alloys with lithium (can be alloyed). Among these, carbonaceous materials, metal composite oxides, or elemental lithium are preferred from the viewpoint of reliability. Active materials that can be alloyed with lithium are preferred in that they enable the production of high-capacity all-solid-state secondary batteries.
[0044] Carbonaceous materials used as negative electrode active materials are materials that consist substantially of carbon. Examples include petroleum pitch, carbon black such as acetylene black (AB), graphite (natural graphite, artificial graphite such as vapor-grown graphite, etc.), and carbonaceous materials obtained by firing various synthetic resins such as PAN (polyacrylonitrile) resins or furfuryl alcohol resins. Furthermore, examples include various types of carbon fibers such as PAN-based carbon fibers, cellulose-based carbon fibers, pitch-based carbon fibers, vapor-grown carbon fibers, dehydrated PVA (polyvinyl alcohol)-based carbon fibers, lignin carbon fibers, glassy carbon fibers, and activated carbon fibers, as well as mesophase microspheres, graphite whiskers, and plate-shaped graphite. These carbonaceous materials can also be classified into hard carbonaceous materials (also called hard carbon) and graphite-based carbonaceous materials depending on the degree of graphitization. Furthermore, it is preferable that the carbonaceous materials have the interplanar spacing or density and crystallite size described in Japanese Patent Publication No. 62-22066, Japanese Patent Publication No. 2-6856, and Japanese Patent Publication No. 3-45473. The carbonaceous material does not have to be a single material; a mixture of natural graphite and artificial graphite as described in Japanese Patent Publication No. 5-90844, graphite with a coating layer as described in Japanese Patent Publication No. 6-4516, etc., can also be used. As the carbonaceous material, hard carbon or graphite is preferably used, and graphite is more preferably used.
[0045] The oxides of metals or metalloid elements used as negative electrode active materials are not particularly limited as long as they are oxides capable of intercalating and releasing lithium, and include oxides of metal elements (metal oxides), composite oxides of metal elements or composite oxides of metal elements and metalloid elements (collectively referred to as metal composite oxides), and oxides of metalloid elements (metalloid oxides). Among these oxides, amorphous oxides are preferred, and chalcogenides, which are reaction products of metal elements and elements of Group 16 of the periodic table, are also preferred. In the present invention, metalloid elements refer to elements that exhibit properties intermediate between metal elements and nonmetalloid elements, and usually include the six elements boron, silicon, germanium, arsenic, antimony, and tellurium, and further include the three elements selenium, polonium, and astatine. Furthermore, amorphous means having a broad scattering band with peaks in the region of 20° to 40° at 2θ values in X-ray diffraction using CuKα rays, and may have crystalline diffraction lines. Preferably, the strongest intensity of the crystalline diffraction lines observed at 40° to 70° in 2θ values is 100 times or less, more preferably 5 times or less, the intensity of the diffraction line at the peak of the broad scattering band observed at 20° to 40° in 2θ values, and it is particularly preferable that there are no crystalline diffraction lines.
[0046] Among the group of compounds consisting of the amorphous oxides and chalcogenides described above, amorphous oxides of metalloid elements or the chalcogenides described above are more preferred, and oxides (compounds) consisting of one element selected from groups 13(IIIB) to 15(VB) of the periodic table (for example, Al, Ga, Si, Sn, Ge, Pb, Sb, and Bi) or a combination of two or more of these elements, or chalcogenides are particularly preferred. Specific examples of preferred amorphous oxides and chalcogenides include, for example, Ga2O3, GeO, PbO, PbO2, Pb2O3, Pb2O4, Pb3O4, Sb2O3, Sb2O4, Sb2O8Bi2O3, Sb2O8Si2O3, Sb2O5, Bi2O3, Bi2O4, GeS, PbS, PbS2, Sb2S3, or Sb2S5. Suitable negative electrode active materials that can be used in combination with amorphous oxides mainly composed of Sn, Si, and Ge include carbonaceous materials capable of intercalating and / or releasing lithium ions or lithium metal, elemental lithium, lithium alloys, and negative electrode active materials that can be alloyed with lithium.
[0047] From the viewpoint of high current density charge-discharge characteristics, oxides of metals or metalloid elements, particularly metal (composite) oxides and the chalcogenides, preferably contain at least one of titanium and lithium as constituent components. Examples of lithium-containing metal composite oxides (lithium composite metal oxides) include composite oxides of lithium oxide and the above-mentioned metal (composite) oxide or chalcogenide, more specifically, Li2SnO2. The negative electrode active material, for example, a metal oxide, is also preferably one that contains titanium (titanium oxide). Specifically, Li4Ti5O 12 Lithium titanate [LTO] is preferable because it exhibits excellent rapid charge-discharge characteristics due to its small volume fluctuation during lithium ion intercalation and deintercalation, which suppresses electrode degradation and improves the lifespan of lithium-ion secondary batteries.
[0048] The lithium alloy used as the negative electrode active material is not particularly limited as long as it is an alloy commonly used as the negative electrode active material in secondary batteries. For example, lithium aluminum alloy, specifically a lithium aluminum alloy in which lithium is the base metal and 10% by mass of aluminum is added, is an example.
[0049] The negative electrode active material capable of forming an alloy with lithium is not particularly limited as long as it is one that is conventionally and ordinarily used as a negative electrode active material for secondary batteries. Such an active material undergoes significant expansion and contraction during charging and discharging of an all-solid secondary battery, which accelerates the deterioration of cycle characteristics. However, since the electrode composition of the present invention contains polymer binders A and B described later, the deterioration of cycle characteristics can be suppressed. Examples of such active materials include (negative electrode) active materials (alloys and the like) containing elemental silicon or elemental tin, and respective metals such as Al and In. A negative electrode active material containing elemental silicon (elemental silicon-containing active material) that enables a higher battery capacity is preferred, and an elemental silicon-containing active material in which the content of elemental silicon accounts for 50 mol% or more of all constituent elements is more preferred. In general, negative electrodes containing these negative electrode active materials (for example, a Si negative electrode containing an elemental silicon-containing active material, a Sn negative electrode containing an active material having elemental tin, etc.) can occlude more Li ions than carbon negative electrodes (such as graphite and acetylene black). That is, the occlusion amount of Li ions per unit mass increases. Therefore, the battery capacity (energy density) can be increased. As a result, there is an advantage that the battery operation time can be extended. Examples of the elemental silicon-containing active material include silicon materials such as Si and SiOx (0<x≦1), silicon-containing alloys further containing titanium, vanadium, chromium, manganese, nickel, copper, lanthanum and the like (for example, LaSi₂, VSi₂, La-Si, Gd-Si, Ni-Si), structured active materials (for example, LaSi₂ / Si), and other active materials containing elemental silicon and elemental tin such as SnSiO₃ and SnSiS₃. Note that SiOx can be used per se as a negative electrode active material (a semi-metal oxide), and can also be used as a negative electrode active material (its precursor substance) that can be alloyed with lithium, since Si is generated by the operation of the all-solid secondary battery. Examples of the negative electrode active material having elemental tin include Sn, SnO, SnO₂, SnS, SnS₂, and further the aforementioned active materials containing elemental silicon and elemental tin. A composite oxide with lithium oxide, for example, Li₂SnO₂, can also be mentioned.
[0050] In the present invention, the above-mentioned negative electrode active material can be used without particular limitation, but in terms of battery capacity, a negative electrode active material that can be alloyed with lithium is preferred as the negative electrode active material, and among these, the above-mentioned silicon material or silicon-containing alloy (alloy containing the element silicon) is more preferred, and it is even more preferred to contain silicon (Si) or a silicon-containing alloy.
[0051] The negative electrode active material contained in the electrode composition of the present invention is preferably in particulate form within the electrode composition. The shape of the particles is not particularly limited and may be flattened, amorphous, etc., but spherical or granular is preferred. When the negative electrode active material is in particulate form, the particle size (volume-average particle size) of the negative electrode active material is not particularly limited, but is preferably 0.1 to 60 μm, and more preferably 0.5 to 10 μm. The particle size of the negative electrode active material particles can be adjusted in the same manner as the particle size of the inorganic solid electrolyte, and the measurement method can also be the same as that for the particle size of the inorganic solid electrolyte.
[0052] The electrode composition of the present invention may contain one or more negative electrode active materials. The content of the negative electrode active material in the electrode composition is not particularly limited and can be determined as appropriate. For example, it is preferably 10 to 90% by mass, more preferably 20 to 85% by mass, even more preferably 30 to 80% by mass, and still more preferably 40 to 75% by mass, based on 100% by mass of solid content.
[0053] In this invention, the negative electrode active material layer can also be formed by charging a secondary battery. In this case, instead of the negative electrode active material, ions of metals belonging to Group 1 or Group 2 of the periodic table that are generated in the all-solid-state secondary battery can be used. By combining these ions with electrons and depositing them as a metal, the negative electrode active material layer can be formed.
[0054] The chemical formula of the compound obtained by the above calcination method can be calculated using inductively coupled plasma (ICP) emission spectroscopy as a measurement method, or, as a simpler method, from the mass difference of the powder before and after calcination.
[0055] (Coating of active material) The surfaces of the positive electrode active material and the negative electrode active material may be coated with another metal oxide. Examples of surface coating agents include metal oxides containing Ti, Nb, Ta, W, Zr, Al, Si, or Li. Specifically, examples include spinel titanate, tantalum oxides, niobium oxides, lithium niobate compounds, and more specifically, Li4Ti5O 12 Examples include Li2Ti2O5, LiTaO3, LiNbO3, LiAlO2, Li2ZrO3, Li2WO4, Li2TiO3, Li2B4O7, Li3PO4, Li2MoO4, Li3BO3, LiBO2, Li2CO3, Li2SiO3, SiO2, TiO2, ZrO2, Al2O3, B2O3, etc. Furthermore, the electrode surface containing the positive electrode active material or the negative electrode active material may be surface-treated with sulfur or phosphorus. Furthermore, the particle surfaces of the positive electrode active material or negative electrode active material may be surface-treated with active light or an active gas (such as plasma) before or after the above-mentioned surface coating.
[0056] <Polymer Binder (PB)> The polymer binder (PB) contained in the electrode composition of the present invention contains one or more of the following polymer binder A and one or more of the following polymer binder B. Polymer binder A: Dissolves in dispersion medium (D), has an adsorption rate of 20% or more for the active material (AC) in dispersion medium (D), and is greater than its adsorption rate for the inorganic solid electrolyte (SE). (Hereafter, polymer binder A may be referred to as AC adsorption binder.) Polymer binder B: Dissolves in dispersion medium (D), has an adsorption rate of 20% or more for the inorganic solid electrolyte (SE) in dispersion medium (D), and is greater than its adsorption rate for the active material (AC). (Hereafter, polymer binder B may be referred to as SE adsorption binder.)
[0057] (Polymer Binder A) Polymer binder A exhibits the property of dissolving in the dispersion medium (D) contained in the electrode composition (solubility). A polymer binder that dissolves in the dispersion medium is called a soluble binder. In the electrode composition, polymer binder A usually exists in a dissolved state in the dispersion medium (D), although this depends on its content, the solubility described later, the content of the dispersion medium (D), etc. This allows polymer binder A to stably perform its function of dispersing the active material (AC) in the dispersion medium (D).
[0058] In this invention, a polymer binder (PB) is said to dissolve in the dispersion medium (D) if its solubility in the dispersion medium (D) is 10% by mass or more in solubility measurements. On the other hand, a polymer binder is said not to dissolve in the dispersion medium (insoluble) if its solubility in the dispersion medium (D) is less than 10% by mass in solubility measurements. The method for measuring solubility is as follows. A specified amount of the polymer binder (PB) to be measured is weighed into a glass bottle, and 100 g of the same dispersion medium (D) as that contained in the electrode composition is added thereto. The mixture is stirred at a rotation speed of 80 rpm on a mix rotor at a temperature of 25°C for 24 hours. The transmittance of the resulting mixture after 24 hours of stirring is measured under the following conditions. This test (transmittance measurement) is performed by changing the amount of polymer binder (PB) dissolved (the specified amount above), and the upper limit concentration X (mass%) at which the transmittance is 99.8% is defined as the solubility of the polymer binder (PB) in the above dispersion medium. <Transmittance measurement conditions> Dynamic light scattering (DLS) measurement Equipment: DLS-8000 DLS measuring device manufactured by Otsuka Electronics Laser wavelength, power output: 488nm / 100mW Sample cell: NMR tube
[0059] Polymer binder A has an adsorption rate of A to the active material (AC) in dispersion medium (D). AC The adsorption rate to inorganic solid electrolytes (SE) is 20% or more, and the adsorption rate to inorganic solid electrolytes (SE) is A SEis larger than that. As a result, the polymer binder A can be preferentially adsorbed to the active material (AC) over the inorganic solid electrolyte (SE), so as to improve the dispersion characteristics and binding property of the active material (AC), and the content thereof can also be reduced. Adsorption rate A of polymer binder A AC may be 20% or more, and from the viewpoints of the content of the polymer binder, dispersion stability and binding property, it is preferably 30% or more, more preferably 40% or more, and even more preferably 60% or more. Adsorption rate A AC The upper limit of is not particularly limited, but usually, the adsorption rate A AC increases, the adsorption rate A accordingly SE also increases, which may inhibit the preferential adsorption to the active material (AC). Therefore, the upper limit can be, for example, 95% or less, preferably 90% or less, more preferably 80% or less, and may be 60%. Adsorption rate A of polymer binder A SE is not particularly limited as long as it is smaller than the above adsorption rate A AC , and is appropriately determined according to the value of the adsorption rate A AC . The adsorption rate A SE is, for example, preferably 45% or less, more preferably 35% or less, even more preferably 20% or less, particularly preferably 15% or less, and most preferably 10% or less. In the polymer binder A, the adsorption rate A AC and the adsorption rate A SE The difference (A AC -A SE ) is not particularly limited, and is preferably more than 0%, more preferably 5% or more, and even more preferably 10% or more. The upper limit is not particularly limited, and can be, for example, 30%.
[0060] In the present invention, the adsorption rate (%) of polymer binder (PB), i.e., polymer binder A or B, is a value measured using an active material (AC) or inorganic solid electrolyte (SE) contained in the electrode composition and a specific dispersion medium (D), and is an index indicating the degree to which the polymer binder (PB) adsorbs to the active material (AC) or inorganic solid electrolyte (SE) in this dispersion medium (D). Here, the adsorption of polymer binder (PB) to the active material (AC) or inorganic solid electrolyte (SE) includes not only physical adsorption but also chemical adsorption, as described above. If the electrode composition contains multiple types of active materials (AC) or inorganic solid electrolytes (SE), the adsorption rate is defined as the adsorption rate to the active material (AC) or inorganic solid electrolyte (SE) having the same composition as the active material composition or inorganic solid electrolyte composition (type and content) in the electrode composition. Similarly, if the electrode composition contains multiple types of specific dispersion media (D), the adsorption rate is measured using the dispersion media (D) having the same composition as the specific dispersion media (type and content) in the electrode composition. If the electrode composition contains multiple types of polymer binder A or B, the adsorption rate is measured for each polymer binder.
[0061] Adsorption rate A of polymer binder (PB) to active material (AC) AC The percentage (%) is measured using the active material (AC), polymer binder (PB), and dispersion medium (D) used in the preparation of the electrode composition, as follows. Specifically, 1.6 g of active material (AC) and 0.08 g of polymer binder (PB) are placed in a 15 mL vial, and 8 g of dispersion medium (D) is added while stirring with a mixing rotor. The mixture is then stirred at 80 rpm for 30 minutes at room temperature (25 °C). The dispersion after stirring is filtered through a 1 μm pore size filter, and 2 g is taken from the total 8 g of filtrate, dried, and the mass of the dried polymer binder (PB) (mass of polymer binder (PB) that was not adsorbed by the active material (AC)) BY is measured. From the mass BY of the polymer binder (PB) obtained in this way, and the mass of 0.08 g of polymer binder (PB) used, the adsorption rate A of the polymer binder (PB) to the active material (AC) is calculated using the following formula. ACCalculate (%). The average value of the adsorption rate (%) obtained by performing this measurement twice is defined as the adsorption rate A of the polymer binder (PB) AC (%). Adsorption rate A AC (%) = [(0.08 - BY × 8 / 2) / 0.08] × 100
[0062] The adsorption rate A of the polymer binder (PB) to the inorganic solid electrolyte (SE) SE (%) is measured as follows using the inorganic solid electrolyte (SE), the polymer binder (PB), and the dispersion medium (D) used for preparing the electrode composition. Specifically, 0.5 g of the inorganic solid electrolyte (SE) and 0.26 g of the polymer binder (PB) are placed in a 15 mL vial, 25 g of the dispersion medium (D) is added while stirring with a mix rotor, and the mixture is further stirred at room temperature and 80 rpm for 30 minutes. The stirred dispersion is filtered through a filter with a pore size of 1 μm, 2 g is collected from the total 25 g of the filtrate and dried, and the mass BX of the dried polymer binder (PB) (the mass of the polymer binder (PB) not adsorbed to the inorganic solid electrolyte (SE)) is measured. From the mass BX of the polymer binder (PB) thus obtained and the mass 0.26 g of the polymer binder (PB) used, the adsorption rate A of the polymer binder (PB) to the inorganic solid electrolyte (SE) is calculated by the following formula SE (%). The average value of the adsorption rate (%) obtained by performing this measurement twice is defined as the adsorption rate A of the polymer binder (PB) SE (%). Adsorption rate A SE (%) = [(0.26 - BX × 25 / 2) / 0.26] × 100
[0063] In the present invention, both adsorption rates of the polymer binder A can be appropriately set according to the type of polymer (structure and composition of polymer chains) forming the polymer binder A, the type or content of functional groups contained in the polymer, and the like. Other properties of the polymer binder A will be described later.
[0064] (Polymer Binder B) Polymer binder B exhibits the property of dissolving in the dispersion medium (D) contained in the electrode composition. In the electrode composition, polymer binder B usually exists dissolved in the dispersion medium (D), although this depends on its content, the solubility described later, the content of the dispersion medium (D), etc. This allows polymer binder B to stably perform its function of dispersing the inorganic solid electrolyte (SE) in the dispersion medium (D).
[0065] Polymer binder B has an adsorption rate A of the inorganic solid electrolyte (SE) in the dispersion medium (D). SE The adsorption rate A of the active material (AC) is 20% or more. AC It is larger than [the other component]. As a result, polymer binder B preferentially adsorbs to the inorganic solid electrolyte (SE) rather than the active material (AC), improving the dispersion and binding properties of the inorganic solid electrolyte (SE), and also allowing for a reduction in its content. Adsorption rate A of polymer binder B SE The adsorption rate A is 20% or more, but is preferably 30% or more, more preferably 40% or more, and even more preferably 60% or more, in terms of polymer binder content, dispersion stability and binding properties. SE There is no particular upper limit to the adsorption rate A. SE As it increases, the adsorption rate A AC The amount can also increase, which can inhibit preferential adsorption to inorganic solid electrolytes (SE). Therefore, the upper limit can be, for example, 95% or less, preferably 90% or less, more preferably 80% or less, and can also be 60%. Adsorption rate A of polymer binder B AC The above adsorption rate A SE There are no particular restrictions as long as it is smaller than A, and the adsorption rate A SE The adsorption rate A is determined appropriately according to the value of [the value]. ACFor example, it is preferable that it be 35% or less, more preferably 20% or less, even more preferably 15% or less, and particularly preferably 10% or less. In polymer binder B, adsorption rate A SE and adsorption rate A AC The difference (A SE -A AC The upper limit is not particularly limited, but is preferably greater than 0%, more preferably 5% or more, and even more preferably 10% or more. Adsorption rate A of polymer binder B SE and A AC This value shall be the value calculated by the measurement method described above.
[0066] In a combination of polymer binder A and polymer binder B, the adsorption rate A SE Or A AC The difference is not particularly limited, but the adsorption rate A of polymer binder A and polymer binder B allows for more selective adsorption to the active material (AC). AC The difference (absolute value) is preferably 5% or more, more preferably 10% or more, even more preferably 15% or more, and even more preferably 30% or more. Similarly, the adsorption rates of polymer binder A and polymer binder B are such that more selective adsorption to inorganic solid electrolytes (SE) is possible. SE The difference (absolute value) is preferably 5% or more, more preferably 10% or more, and even more preferably 15% or more. Adsorption rate A AC The difference (absolute value) and the adsorption rate A SE The upper limits of the difference (absolute value) are not particularly restricted and can be determined as appropriate. For example, adsorption rate A AC The difference (absolute value) is preferably 60% or less, and more preferably 50% or less. On the other hand, adsorption rate A SE The difference (absolute value) is preferably 30% or less, more preferably 20% or less, and can also be 10% or less.
[0067] In the present invention, the adsorption rates of polymer binder B can be appropriately set depending on the type of polymer forming polymer binder B (structure and composition of polymer chains), the type or content of functional groups possessed by the polymer, and so on. Further details regarding the properties of polymer binder B will be discussed later.
[0068] - Polymers that form polymer binders A and B - The polymers forming polymer binder A or B are not particularly limited, as long as they impart solubility to the polymer binder in the dispersion medium (D) and satisfy the above adsorption rate to the active material (AC) or inorganic solid electrolyte (SE). Various polymers can be used. Among these, polymers having at least one bond selected from urethane bonds, urea bonds, amide bonds, imide bonds, and ester bonds, or a polymer chain of carbon-carbon double bonds in its main chain, are preferred. In the present invention, a polymer chain of carbon-carbon double bonds refers to a polymer chain formed by the polymerization of carbon-carbon double bonds (ethylenically unsaturated groups), and specifically refers to a polymer chain obtained by polymerization (homopolymerization or copolymerization) of monomers having carbon-carbon unsaturated bonds.
[0069] In this invention, the main chain of a polymer refers to linear molecular chains in which all other molecular chains constituting the polymer can be considered as branched chains or pendant groups relative to the main chain. Although it depends on the mass-average molecular weight of the molecular chains considered as branched chains or pendant chains, typically the longest chain among the molecular chains constituting the polymer becomes the main chain. However, the terminal groups at the ends of the polymer are not included in the main chain. Furthermore, the side chains of a polymer refer to molecular chains other than the main chain, and include short molecular chains and long molecular chains.
[0070] The above-mentioned bonds are not particularly limited as long as they are contained in the main chain of the polymer, and may be contained in a constituent unit (repeating unit) or / or as bonds connecting different constituent units. Furthermore, the above-mentioned bonds contained in the main chain are not limited to one type, but may be two or more types, preferably 1 to 6 types, and more preferably 1 to 4 types. In this case, the bonding pattern of the main chain is not particularly limited, and may have two or more types of bonds randomly, or it may be a segmented main chain with segments having specific bonds and segments having other bonds.
[0071] The main chain having the above-mentioned bonds is not particularly limited, but a main chain having at least one segment of the above-mentioned bonds is preferred, a main chain made of polyamide, polyurea, polyurethane, or (meth)acrylic polymer is more preferred, and a main chain made of polyurethane or (meth)acrylic polymer is even more preferred.
[0072] Examples of polymers having urethane bonds, urea bonds, amide bonds, imide bonds, or ester bonds in their main chain include sequentially polymerized (polycondensation, polyaddition, or addition-condensation) polymers such as polyurethane, polyurea, polyamide, polyimide, and polyester, or copolymers thereof. The copolymer may be a block copolymer in which each of the above polymers is used as a segment, or a random copolymer in which the constituent components of two or more of the above polymers are randomly bonded together. Polymers having a polymer chain of carbon-carbon double bonds as the main chain, that is, polymers having a polymer chain formed by polymerizing monomers having carbon-carbon unsaturated bonds, include chain polymers such as fluoropolymers (fluorine-containing polymers), hydrocarbon polymers, vinyl polymers, and (meth)acrylic polymers. The polymerization mode of these chain polymers is not particularly limited and may be block copolymers, alternating copolymers, or random copolymers.
[0073] The polymer forming the binder may be one type or two or more types.
[0074] The polymer forming the above binder preferably has components represented by any of the following formulas (1-1) to (1-5), and more preferably has components represented by the following formulas (1-1) or (1-2). [ka]
[0075] In formula (1-1), R 1 R represents a hydrogen atom or an alkyl group (the number of carbon atoms is preferably 1 to 12, more preferably 1 to 6, and even more preferably 1 to 3). 1 The alkyl group that can be selected may have substituents. The substituent is not particularly limited, but examples include substituent Z described later, and groups other than the functional group selected from functional group (a) are preferred, such as halogen atoms.
[0076] R 2 This refers to a group having a hydrocarbon group with 4 or more carbon atoms. In the present invention, a group having a hydrocarbon group is a group consisting of the hydrocarbon group itself (where the hydrocarbon group is R 1 It bonds directly to the carbon atom in the above formula. ) and R 2 A group consisting of a carbon atom in the above formula to which is bonded and a linking group that connects the hydrocarbon group (the hydrocarbon group is R 1 It is bonded to the carbon atom in the above formula via a linking group. ) and are included. A hydrocarbon group is a group composed of carbon atoms and hydrogen atoms, and is usually R 2 It is introduced at the end of the molecule. The hydrocarbon group is not particularly limited, but an aliphatic hydrocarbon group is preferred, an aliphatic saturated hydrocarbon group (alkyl group) is more preferred, and a linear or branched alkyl group is even more preferred. The number of carbon atoms in the hydrocarbon group may be 4 or more, preferably 6 or more, more preferably 8 or more, and may also be 10 or more. There is no particular upper limit, but preferably 20 or less, and more preferably 14 or less.
[0077] The above linking groups are not particularly limited, but examples include alkylene groups (preferably with 1 to 12 carbon atoms, more preferably 1 to 6, and even more preferably 1 to 3), alkenylene groups (preferably with 2 to 6 carbon atoms, more preferably 2 to 3), arylene groups (preferably with 6 to 24 carbon atoms, more preferably 6 to 10), oxygen atoms, sulfur atoms, and imino groups (-NR). N -:R N The group represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or an aryl group having 6 to 10 carbon atoms. Examples include a carbonyl group, a phosphate linking group (-OP(OH)(O)-O-), a phosphonic acid linking group (-P(OH)(O)-O-), or a group relating to a combination thereof. A polyalkylene oxy chain can also be formed by combining an alkylene group and an oxygen atom. Preferred linking groups are those formed by combining an alkylene group, an arylene group, a carbonyl group, an oxygen atom, a sulfur atom, and an imino group, and more preferably a group formed by combining an alkylene group, an arylene group, a carbonyl group, an oxygen atom, and an imino group, such as a -CO-O- group or a -CO-N(R N )-group(R N The above is true. A group containing ) is more preferably a -CO-O- group or a -CO-N(R N )-group(R N The above is true. ) is particularly preferred. The number of atoms constituting the linking group and the number of linked atoms are as described later. However, the above does not apply to the polyalkylene oxy chain constituting the linking group. In the present invention, the number of atoms constituting the linking group is preferably 1 to 36, more preferably 1 to 24, even more preferably 1 to 12, and particularly preferably 1 to 6. The number of linked atoms in the linking group is preferably 10 or less, and more preferably 8 or less. The lower limit is 1 or more. The above number of linked atoms refers to the minimum number of atoms that connect predetermined structural parts. For example, in the case of -CH2-C(=O)-O-, the number of atoms constituting the linking group is 6, but the number of linked atoms is 3. The hydrocarbon group and the linking group may or may not have substituents. Examples of substituents that may be present include substituent Z, which is preferably a group other than the functional group selected from functional group (a), and halogen atoms are a suitable example.
[0078] In the above equation (1-1), R 1 The carbon atom adjacent to the carbon atom to which the substituent is bonded has two hydrogen atoms, but in the present invention, it may have one or two substituents. The substituent is not particularly limited, but examples include substituent Z described later, and a group other than the functional group selected from functional group (a) is preferred. The compounds used to derive the constituent components represented by formula (1-1) are not particularly limited, but examples include linear alkyl ester compounds of (meth)acrylate (linear alkyl means alkyl group having 4 or more carbon atoms).
[0079] In equations (1-2) to (1-5), R 3 This refers to a linking group containing a polybutadiene chain or a polyisoprene chain, with a mass-average molecular weight or number-average molecular weight (hereinafter referred to as mass-average molecular weight, etc.) of 500 or more and 200,000 or less. R 3 The ends of the above chain that can be taken as are R 3 The constituent components represented by the above formulas can be appropriately modified to ordinary chemical structures that can be incorporated into them. In each of the above formulas, R 3 Although it is a divalent molecular chain, at least one hydrogen atom may be substituted with -NH-CO-, -CO-, -O-, -NH-, or -N< to form a chain of three or more valents.
[0080] R 3The polybutadiene and polyisoprene chains that can be used as such include known chains made of polybutadiene and polyisoprene, respectively, as long as they satisfy the requirements for mass-average molecular weight, etc. Both of these polybutadiene and polyisoprene chains are diene polymers having double bonds in the main chain, but in the present invention, polymers in which the double bonds have been hydrogenated (reduced) (for example, non-diene polymers that do not have double bonds in the main chain) are also included. In the present invention, hydrides of polybutadiene or polyisoprene chains are preferred. The polybutadiene chain and polyisoprene chain, as raw material compounds, preferably have reactive groups at their ends, and more preferably have polymerizable terminal reactive groups. The polymerizable terminal reactive groups, upon polymerization, form the R of each of the above formulas. 3 A group is formed that bonds to the terminal reactive group. Examples of such terminal reactive groups include hydroxyl groups, carboxyl groups, and amino groups, with hydroxyl groups being preferred. Suitable examples of polybutadiene and polyisoprene having terminal reactive groups include the NISSO-PB series (manufactured by Nippon Soda Co., Ltd.), Claysol series (manufactured by Tomoe Engineering Co., Ltd.), PolyVEST-HT series (manufactured by Evonik Corporation), poly-bd series (manufactured by Idemitsu Kosan Co., Ltd.), poly-ip series (manufactured by Idemitsu Kosan Co., Ltd.), and EPOL (manufactured by Idemitsu Kosan Co., Ltd.), all of which are trade names.
[0081] R 3 The above-mentioned chains that can be used as such preferably have a mass-average molecular weight (in polystyrene terms) of 500 to 200,000. The lower limit is preferably 500 or more, more preferably 700 or more, and even more preferably 1,000 or more. The upper limit is preferably 100,000 or less, and more preferably 10,000 or less. The mass-average molecular weight is measured using the method described later for the raw material compound before it is incorporated into the main chain of the polymer.
[0082] The content of any of the components represented by formulas (1-1) to (1-5) in the polymer is not particularly limited, but is preferably 10 to 100 mol%. The content of the component represented by formula (1-1) is more preferably 30 to 98 mol%, and even more preferably 50 to 95 mol%, in terms of dispersion stability, binding properties, etc. The content of any of the components represented by formulas (1-2) to (1-5) is more preferably 30 to 98 mol%, and even more preferably 50 to 95 mol%, in terms of dispersion stability, etc. On the other hand, in terms of improving binding properties, it is preferably 0 to 90 mol%, more preferably 10 to 80 mol%, and even more preferably 20 to 70 mol%.
[0083] (Component having a functional group selected from functional group (a)) The polymer forming at least one of polymer binder A and polymer binder B preferably contains a component having a functional group selected from the following functional group (a) as a substituent. In particular, the polymer forming polymer binder B preferably contains a component having a functional group selected from the following functional group (a). The component having the functional group has the function of improving the adsorption rate of the binder and may be any component forming the polymer. The functional group may be incorporated into the main chain of the polymer or into the side chain. When incorporated into the side chain, the functional group may be directly bonded to the main chain or bonded via the linking group. The linking group is not particularly limited, but examples of linking groups described later are included.
[0084] <Functional group group (a)> Hydroxyl group, amino group, carboxyl group, sulfo group, phosphate group, phosphonic acid group, sulfanyl group, ether bond (-O-), imino group (=NR, -NR-), ester bond (-CO-O-), amide bond (-CO-NR-), imide group (-CO-NR-CO-), urethane bond (-NR-CO-O-), urea bond (-NR-CO-NR-), heterocyclic group, aryl group, carboxylic anhydride group The functional group (a) preferably consists of a hydroxyl group, an amino group, a carboxyl group, a sulfo group, a phosphate group, a phosphonic acid group, a sulfanyl group, an ether bond, an imino group, an amide bond, an imide group, a urethane bond, a urea bond, a heterocyclic group, an aryl group, and a carboxylic anhydride group.
[0085] The amino group, sulfo group, phosphate group (phosphoryl group), heterocyclic group, and aryl group included in functional group (a) are not particularly limited, but are synonymous with the corresponding group of substituent Z described later. However, the number of carbon atoms in the amino group is more preferably 0 to 12, even more preferably 0 to 6, and particularly preferably 0 to 2. The phosphonic acid group is not particularly limited, but examples include phosphonic acid groups with 0 to 20 carbon atoms. When an amino group, ether bond, imino group (-NR-), ester bond, amide bond, imide group, urethane bond, urea bond, etc. are included in the ring structure, it is classified as a heterocyclic group. The heterocyclic group containing an imide group in the ring structure is not particularly limited, but examples include the carboxylic anhydride group described later, for example, the "-CO-O-CO-" group in formula (2a) or formula (2b) is "-CO-NR I One example is a ring modified with a -CO- group. Here, R I represents a hydrogen atom or a substituent. The substituent is not particularly limited and can be selected from substituent Z described later, with alkyl groups being preferred. Hydroxyl groups, amino groups, carboxyl groups, sulfo groups, phosphate groups, phosphonic acid groups, and sulfanyl groups may form salts. In each bond, R represents either a hydrogen atom or a substituent, with a hydrogen atom being preferred. The substituent is not particularly limited and can be selected from substituents Z described later, with alkyl groups being preferred. R in the imide group I As stated above.
[0086] The carboxylic acid anhydride group is not particularly limited, but includes groups obtained by removing one or more hydrogen atoms from a carboxylic acid anhydride (for example, a group represented by formula (2a) below), and also the constituent components themselves obtained by copolymerizing polymerizable carboxylic acid anhydrides as copolymerizable compounds (for example, a constituent component represented by formula (2b) below). As for groups obtained by removing one or more hydrogen atoms from a carboxylic acid anhydride, groups obtained by removing one or more hydrogen atoms from a cyclic carboxylic acid anhydride are preferred. Carboxylic acid anhydride groups derived from cyclic carboxylic acid anhydrides also correspond to heterocyclic groups, but in this invention they are classified as carboxylic acid anhydrides. Examples include acyclic carboxylic acid anhydrides such as acetic anhydride, propionic anhydride, and benzoic anhydride, and cyclic carboxylic acid anhydrides such as maleic anhydride, phthalic anhydride, fumaric anhydride, and succinic anhydride. The polymerizable carboxylic acid anhydride is not particularly limited, but includes carboxylic acid anhydrides having an unsaturated bond in the molecule, and is preferably a polymerizable cyclic carboxylic acid anhydride. Specifically, maleic anhydride is an example. Examples of carboxylic acid anhydride groups include the group represented by formula (2a) or the component represented by formula (2b) below, but the present invention is not limited to these. In each formula, * indicates a bond position.
[0087] [ka]
[0088] In sequentially polymerized polymers, ester bonds (-CO-O-), amide bonds (-CO-NR-), urethane bonds (-NR-CO-O-), and urea bonds (-NR-CO-NR-) are represented by being divided into -CO- and -O- groups, -CO and -NR- groups, -NR-CO- and -O- groups, and -NR-CO- and -NR- groups, respectively, when the chemical structure of the polymer is represented by components derived from the raw material compounds. Therefore, in this invention, the components having these bonds are defined as components derived from carboxylic acid compounds or isocyanate compounds, regardless of the polymer's designation, and do not include components derived from polyols or polyamine compounds. Furthermore, in chain polymers, components having ester bonds (excluding ester bonds that form carboxyl groups) refer to components in which ester bonds are not directly bonded to atoms constituting the main chain of the chain polymer, or to the main chain of the polymerization chain incorporated into the chain polymer as a branched chain or pendant chain (for example, the polymerization chain of a macromonomer), and do not include, for example, components derived from alkyl (meth)acrylate. In the present invention, it is preferable that amino groups, ether bonds, imino groups, ester bonds, amide bonds, urethane bonds, urea bonds, heterocyclic groups, and aryl groups are incorporated into the branched chain of the polymer. A single component may have one or more functional groups, and if it has two or more, they may or may not be bonded to each other. Furthermore, there is no particular limit to the number of functional groups a single component may have; it may be one or more, and can range from one to four.
[0089] The linking group that connects the functional group to the main chain is not particularly limited, but any linking group other than the following particularly preferred linking groups is R in formula (1-1) above. 2 This is synonymous with a linking group in a group having a hydrocarbon group with 4 or more carbon atoms, which can be adopted as such. Particularly preferred linking groups for bonding the functional group and the main chain are the -CO-O- group or the -CO-N(R N )-group(R N As described above, it is a group formed by combining () with an alkylene group or a polyalkylene oxy chain.
[0090] The constituent components having the above-mentioned functional group are not particularly limited as long as they have the above-mentioned functional group, but examples include constituent components obtained by introducing the above-mentioned functional group into a constituent component represented by any of the above-mentioned formulas (1-1) to (1-5), constituent components represented by formula (I-1) or formula (I-2) described later, constituent components derived from a compound represented by formula (I-5) described later, constituent components obtained by introducing the above-mentioned functional group into a constituent component represented by formula (I-3) or formula (I-4) described later, or a constituent component derived from a compound represented by formula (I-6), furthermore, (meth)acrylic compounds (M1) or other polymerizable compounds (M2) described later, constituent components obtained by introducing the above-mentioned functional group into a constituent component represented by any of the above-mentioned formulas (b-1) to (b-3) described later. The compounds that yield the constituent components having the above-mentioned functional groups are not particularly limited, but examples include compounds obtained by introducing the above-mentioned functional groups into (meth)acrylate short-chain alkyl ester compounds (short-chain alkyl means alkyl group with 3 or fewer carbon atoms).
[0091] The content of the component having the above-mentioned functional group in the polymer is not particularly limited. For sequential polymers, the content is preferably 0.01 to 50 mol%, more preferably 0.1 to 50 mol%, and even more preferably 0.3 to 50 mol%, in terms of solid particle dispersion characteristics and binding properties. For chain polymers, the content is preferably 0.01 to 80 mol%, more preferably 0.01 to 70 mol%, even more preferably 0.1 to 50 mol%, and particularly preferably 0.3 to 50 mol%, in terms of solid particle dispersion characteristics and binding properties. The upper limit of the content can also be 30 mol% or less or 10 mol% or less. For sequential polymers and chain polymers, the lower limit of the content can also be 1 mol% or more, 5 mol% or more, or 20 mol% or more.
[0092] - Sequential polymerization polymer - The step-by-step polymer used to form the binder is preferably a component having a functional group selected from the functional group group (a) or a component represented by any of the above formulas (1-2) to (1-5), and may also have components other than these. Among the components shown below, the component represented by formula (I-1) or formula (I-2), and the component derived from the compound represented by formula (I-5) also correspond to components having a functional group selected from the functional group group (a), but will be explained together with the other components. Examples of other components include one or more (preferably 1 to 8, more preferably 1 to 4) components represented by the following formulas (I-1) or (I-2), and furthermore, components represented by the following formulas (I-3) or (I-4), or components obtained by step-by-step polymerization of a carboxylic acid dianhydride represented by the following formula (I-5) and a diamine compound that leads to the component represented by the following formula (I-6). The combination of each component is appropriately selected depending on the polymer type. When referring to a combination of constituent components, one constituent component means a constituent component represented by one of the following formulas. Even if a combination contains two constituent components represented by one of the following formulas, it will not be interpreted as two constituent components.
[0093] [ka]
[0094] In the formula, R P1 and R P2 Each of these represents a molecular chain with a (mass-average) molecular weight of 20 to 200,000. The molecular weight of this molecular chain cannot be uniquely determined as it depends on its type, etc., but for example, 30 or more is preferred, 50 or more is more preferred, 100 or more is even more preferred, and 150 or more is particularly preferred. As an upper limit, 100,000 or less is preferred, and 10,000 or less is more preferred. The molecular weight of the molecular chain is measured for the raw material compound before it is incorporated into the polymer main chain. R P1 and R P2The molecular chains that can be used are not particularly limited, but hydrocarbon chains, polyalkylene oxide chains, polycarbonate chains, or polyester chains are preferred, hydrocarbon chains or polyalkylene oxide chains are more preferred, and hydrocarbon chains, polyethylene oxide chains, or polypropylene oxide chains are even more preferred.
[0095] R P1 and R P2 A hydrocarbon chain can be defined as a hydrocarbon chain composed of carbon atoms and hydrogen atoms, and more specifically, a structure in which at least two atoms (e.g., hydrogen atoms) or groups (e.g., methyl groups) of a compound composed of carbon atoms and hydrogen atoms have been removed. However, in the present invention, a hydrocarbon chain also includes chains having groups containing oxygen atoms, sulfur atoms, or nitrogen atoms in the chain, such as the hydrocarbon group represented by the following formula (M2). Terminal groups that may be present at the ends of a hydrocarbon chain are not included in the hydrocarbon chain. This hydrocarbon chain may have carbon-carbon unsaturated bonds and may have a ring structure of an aliphatic ring and / or an aromatic ring. That is, a hydrocarbon chain can be any hydrocarbon chain composed of hydrocarbons selected from aliphatic hydrocarbons and aromatic hydrocarbons.
[0096] Such hydrocarbon chains can be any chain that satisfies the above molecular weight requirement, and include both chains consisting of low molecular weight hydrocarbon groups and hydrocarbon chains consisting of hydrocarbon polymers (also called hydrocarbon polymer chains). Low molecular weight hydrocarbon chains are chains consisting of ordinary (non-polymerizable) hydrocarbon groups, such as aliphatic or aromatic hydrocarbon groups. Specifically, alkylene groups (preferably with 1 to 12 carbon atoms, more preferably 1 to 6, and even more preferably 1 to 3 carbon atoms), arylene groups (preferably with 6 to 22 carbon atoms, more preferably 6 to 14, and even more preferably 6 to 10 carbon atoms), or combinations thereof are preferred. P2As hydrocarbon groups that can form a low molecular weight hydrocarbon chain, alkylene groups are more preferred, alkylene groups having 2 to 6 carbon atoms are even more preferred, and alkylene groups having 2 or 3 carbon atoms are particularly preferred. This hydrocarbon chain may have polymerization chains (e.g., (meth)acrylic polymers) as substituents.
[0097] The aliphatic hydrocarbon group is not particularly limited and includes, for example, hydrogen-reduced aromatic hydrocarbon groups represented by the following formula (M2), and substructures of known aliphatic diisocyanate compounds (e.g., groups consisting of isophorone). Aromatic hydrocarbon groups include, for example, the hydrocarbon groups possessed by the constituent components of each example listed below, and preferred are arylene groups (for example, groups obtained by removing one or more hydrogen atoms from the aryl group listed in substituent Z below, specifically phenylene groups, torylene groups, or xylylene groups) or hydrocarbon groups represented by the following formula (M2).
[0098] [ka]
[0099] In formula (M2), X represents a single bond, -CH2-, -C(CH3)2-, -SO2-, -S-, -CO-, or -O-, and from the viewpoint of binding properties, -CH2- or -O- is preferred, and -CH2- is more preferred. The alkylene group and methyl group exemplified herein may be substituted with substituent Z, preferably a halogen atom (more preferably a fluorine atom). R M2 ~R M5 Each of these is a hydrogen atom or a substituent, with hydrogen atoms being preferred. M2 ~R M5 The substituents that can be used are not particularly limited, but for example, alkyl groups having 1 to 20 carbon atoms, alkenyl groups having 1 to 20 carbon atoms, -OR M6 ,―N(R M6 )2, -SR M6 (R M6represents a substituent, preferably an alkyl group having 1 to 20 carbon atoms or an aryl group having 6 to 10 carbon atoms. Examples include halogen atoms (e.g., fluorine atom, chlorine atom, bromine atom). -N(R M6 )2 may include an alkylamino group (preferably with 1 to 20 carbon atoms, more preferably 1 to 6 carbon atoms) or an arylamino group (preferably with 6 to 40 carbon atoms, more preferably 6 to 20 carbon atoms).
[0100] The hydrocarbon polymer chain is a polymer chain formed by the polymerization of polymerizable hydrocarbons (at least two of them), and is not particularly limited as long as it is a chain made of a hydrocarbon polymer with a larger number of carbon atoms than the low molecular weight hydrocarbon chain described above, but is preferably a chain made of a hydrocarbon polymer composed of 30 or more carbon atoms, more preferably 50 or more carbon atoms. The upper limit of the number of carbon atoms that make up the hydrocarbon polymer is not particularly limited and can be, for example, 3,000. The hydrocarbon polymer chain is preferably a chain in which the main chain is made of a hydrocarbon polymer composed of aliphatic hydrocarbons that satisfy the above number of carbon atoms, and is more preferably a chain made of a polymer (preferably an elastomer) composed of aliphatic saturated hydrocarbons or aliphatic unsaturated hydrocarbons. Specifically, examples of polymers include diene polymers having double bonds in the main chain and non-diene polymers not having double bonds in the main chain. Examples of diene polymers include styrene-butadiene copolymers, styrene-ethylene-butadiene copolymers, isobutylene and isoprene copolymers (preferably butyl rubber (IIR)), ethylene-propylene-diene copolymers, etc. Examples of non-diene polymers include olefin polymers such as ethylene-propylene copolymers and styrene-ethylene-butylene copolymers, as well as hydrogen-reduced products of the above-mentioned diene polymers.
[0101] The hydrocarbons forming the hydrocarbon chain preferably have reactive groups at their ends, and more preferably have terminal reactive groups that can be condensed or polyadded. The terminal reactive groups that can be condensed or polyadded can be used to form the R of each of the above formulas by condensation or polyaddition. P1 or R P2It forms a group that bonds to the terminal. Examples of such terminal reactive groups include isocinate groups, hydroxyl groups, carboxyl groups, amino groups, and acid anhydrides, with hydroxyl groups being preferred among them. Suitable hydrocarbon polymers having terminal reactive groups include, for example, the NISSO-PB series (manufactured by Nippon Soda Co., Ltd.), Claysol series (manufactured by Tomoe Engineering Co., Ltd.), PolyVEST-HT series (manufactured by Evonik Corporation), poly-bd series (manufactured by Idemitsu Kosan Co., Ltd.), poly-ip series (manufactured by Idemitsu Kosan Co., Ltd.), EPOL (manufactured by Idemitsu Kosan Co., Ltd.), and Polytail series (manufactured by Mitsubishi Chemical Corporation), all of which are trade names.
[0102] Examples of polyalkylene oxide chains (polyalkylene oxy chains) include known chains composed of polyalkylene oxy groups. The number of carbon atoms in the alkylene oxy group in the polyalkylene oxy chain is preferably 1 to 10, more preferably 1 to 6, and even more preferably 2 or 3 (polyethylene oxy chain or polypropylene oxy chain). The polyalkylene oxy chain may be a chain composed of one type of alkylene oxy group, or a chain composed of two or more types of alkylene oxy groups (for example, a chain composed of an ethylene oxy group and a propylene oxy group). Examples of polycarbonate chains or polyester chains include known chains made of polycarbonate or polyester. The polyalkylene oxy chain, polycarbonate chain, or polyester chain each preferably has an alkyl group at its terminal (preferably with 1 to 12 carbon atoms, and more preferably with 1 to 6 carbon atoms). R P1 and R P2 The ends of the polyalkylene oxy chain, polycarbonate chain, and polyester chain that can be taken as are R P1 and R P2 The components represented by the above formulas can be appropriately modified to have a normal chemical structure that can be incorporated into them. For example, the polyalkylene oxy chain can be modified by removing the terminal oxygen atom to form the R of the above components. P1 or R P2 It will be incorporated as such.
[0103] The alkyl group contained in the molecular chain may have an ether group (-O-), a thioether group (-S-), a carbonyl group (>C=O), or an imino group (>NR) inside or at its terminal. N :R N (These may have a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or an aryl group having 6 to 10 carbon atoms.) In each of the above formulas, R P1 and R P2 Although it is a divalent molecular chain, at least one hydrogen atom may be substituted with -NH-CO-, -CO-, -O-, -NH-, or -N< to form a molecular chain of three or more valents.
[0104] R P1 Among the molecular chains described above, hydrocarbon chains are preferred, low molecular weight hydrocarbon chains are more preferred, hydrocarbon chains consisting of aliphatic or aromatic hydrocarbon groups are even more preferred, and hydrocarbon chains consisting of aliphatic hydrocarbon groups are particularly preferred. R P2 Among the molecular chains mentioned above, low molecular weight hydrocarbon chains (more preferably aliphatic hydrocarbon groups), or molecular chains other than low molecular weight hydrocarbon chains (more preferably polyalkylene oxide chains) are preferred.
[0105] Specific examples of the constituent components represented by the above formula (I-1) are shown below and in the examples. Furthermore, examples of raw material compounds (diisocyanate compounds) for which the constituent components represented by the above formula (I-1) can be derived include the diisocyanate compound represented by formula (M1) and its specific examples, as described in International Publication No. 2018 / 020827, as well as polymeric 4,4'-diphenylmethane diisocyanate. It should be noted that in the present invention, the constituent components represented by formula (I-1) and the raw material compounds for which they are derived are not limited to those described in the following specific examples, examples, and the above-mentioned literature.
[0106] [ka]
[0107] The starting compound (carboxylic acid or its acid chloride, etc.) that leads to the component represented by the above formula (I-2) is not particularly limited, and examples include carboxylic acid or acid chloride compounds and specific examples thereof (e.g., adipic acid or its esterified products) as described in paragraph
[0074] of International Publication No. 2018 / 020827.
[0108] Specific examples of the constituent components represented by formula (I-3) or formula (I-4) are shown below and in the examples. Furthermore, the raw material compounds (diol compounds or diamine compounds) used to derive the constituent components represented by formula (I-3) or formula (I-4) are not particularly limited, and examples include the compounds and specific examples thereof described in International Publication No. 2018 / 020827, as well as dihydroxyoxamide. In this invention, the constituent components represented by formula (I-3) or formula (I-4) and the raw material compounds used to derive them are not limited to those described in the specific examples below, the exemplary polymers described later, the examples, and the above-mentioned literature. In the specific examples below, if a component has a repeating structure, the number of repeats is an integer of 1 or more, and is set appropriately within the range that satisfies the molecular weight or number of carbon atoms of the molecular chain.
[0109] [ka]
[0110] In equation (I-5), R P3 The linking group represents an aromatic or aliphatic linking group (tetravalent), and a linking group represented by any of the following formulas (i) to (iix) is preferred.
[0111] [ka]
[0112] In formulas (i) to (iix), X 1represents a single bond or a divalent linking group. A divalent linking group is preferably an alkylene group having 1 to 6 carbon atoms (e.g., methylene, ethylene, propylene). As propylene, 1,3-hexafluoro-2,2-propanediyl is preferred. L represents -CH2=CH2- or -CH2-. X and R Y Each represents a hydrogen atom or substituent. In each formula, * indicates the bonding site with the carbonyl group in formula (I-5). X and R Y The substituents that can be taken are not particularly limited, and examples of substituent Z described later include alkyl groups (preferably with 1 to 12 carbon atoms, more preferably with 1 to 6 carbon atoms, and still more preferably with 1 to 3 carbon atoms) or aryl groups (preferably with 6 to 22 carbon atoms, more preferably with 6 to 14 carbon atoms, and still more preferably with 6 to 10 carbon atoms).
[0113] The carboxylic acid dianhydride represented by formula (I-5) and the starting compound (diamine compound) from which the constituent component represented by formula (I-6) is derived are not particularly limited, and examples include the compounds described in International Publication No. 2018 / 020827 and International Publication No. 2015 / 046313 and specific examples thereof.
[0114] R P1 , R P2 and R P3 Each of these may have substituents. These substituents are not particularly limited and include, for example, substituent Z described later, or each of the groups included in the above functional group group (a), and R M2 The above substituents that can be adopted are preferably listed.
[0115] If the polymer forming the binder is a stepwise polymer, it may have a component represented by any of the above formulas (1-1) to (1-5), preferably a component having a functional group selected from functional group group (a) (including the component represented by the following formula (I-1)), and may also have a component represented by the above formulas (I-3), (I-4), or (I-5). Examples of the component represented by formula (I-3) include components represented by at least one of the following formulas (I-3A) to (I-3C). The component represented by formula (I-4) is similar to the component represented by formula (I-3), but in each of the following formulas (I-3A) to (I-3C), an oxygen atom is replaced with a nitrogen atom.
[0116] [ka] In equation (I-1), R P1 As stated above, in equation (I-3A), R P2A R represents a chain consisting of low molecular weight hydrocarbon groups (preferably aliphatic hydrocarbon groups). In formula (I-3B), R P2B R represents a polyalkylene oxy chain. In formula (I-3C), R P2C R represents a hydrocarbon polymer chain. P2A A chain consisting of low molecular weight hydrocarbon groups that can be taken as R P2B Polyalkylene oxy chains and R that can be taken as such P2C The hydrocarbon polymer chains that can be used are, respectively, R in formula (I-3) above. P2 This is synonymous with aliphatic hydrocarbon groups, polyalkylene oxy chains, and hydrocarbon polymer chains that can be taken as such, and the preferred ones are also the same.
[0117] The polymer forming the binder (sequentially polymerized polymer) may have components other than those represented by the above formulas. Such components are not particularly limited as long as they can be sequentially polymerized with the raw material compounds that derive the components represented by the above formulas.
[0118] The total content of each of the constituent components represented by formulas (I-1) to (I-6) in the polymer forming the binder is not particularly limited, but is preferably 5 to 100 mol%, more preferably 5 to 80 mol%, and even more preferably 10 to 60 mol%. The upper limit of this content can be, for example, 100 mol% or less, notwithstanding the above 60 mol%. The content of components other than those represented by the above formulas in the polymer forming the binder is not particularly limited, but is preferably 50 mol% or less.
[0119] If the polymer forming the binder has a component represented by any of the above formulas (I-1) to (I-6), the content thereof is not particularly limited and can be appropriately selected and set to the following range, for example. In other words, the content of the component represented by formula (I-1) or formula (I-2), or the component derived from the carboxylic acid dianhydride represented by formula (I-5), in the polymer forming the binder is not particularly limited, but it is preferable that it is the same as the content of the functional group component mentioned above. The content of the constituent component represented by formula (I-3), formula (I-4), or formula (I-6) in the polymer forming the binder is not particularly limited, but is preferably 1 to 80 mol%, more preferably 10 to 80 mol%, even more preferably 20 to 70 mol%, and particularly preferably 30 to 60 mol%. The content of each component represented by any of the above formulas (I-3A) to (I-3C) is set appropriately, taking into consideration the content of the component represented by the above formula (I-3).
[0120] Furthermore, if the polymer forming the binder has multiple constituent components represented by each formula, the above content of each constituent component shall be the total content.
[0121] The polymers forming the binder described above (each component and raw material compound) may have substituents. While there are no particular limitations on substituents, preferred substituents are those selected from the substituent Z listed below.
[0122] The polymer forming the binder described above can be synthesized by selecting raw material compounds according to known methods depending on the type of bonds in the main chain, and then performing polyaddition or condensation polymerization on the raw material compounds. For example, see International Publication No. 2018 / 151118 for synthesis methods. The method for incorporating functional groups is not particularly limited and includes, for example, copolymerizing a compound having a functional group selected from functional group group (a), using a polymerization initiator having (or producing) the above-mentioned functional group, and utilizing polymer reactions.
[0123] As polymers that can be used to form the above-mentioned binder, examples of polyurethanes, polyureas, polyamides, and polyimides include those described below as exemplary polymers and those synthesized in the examples, as well as the polymers described in International Publication No. 2018 / 020827, International Publication No. 2015 / 046313, and Japanese Patent Application Publication No. 2015-088480.
[0124] - Substituent Z - Alkyl groups (preferably C1-C20 alkyl groups, e.g., methyl, ethyl, isopropyl, t-butyl, pentyl, heptyl, 1-ethylpentyl, benzyl, 2-ethoxyethyl, 1-carboxymethyl, etc.), alkenyl groups (preferably C2-C20 alkenyl groups, e.g., vinyl, allyl, oleyl, etc.), alkynyl groups (preferably C2-C20 alkynyl groups, e.g., ethynyl, butadiinyl, phenylethynyl, etc.), cycloalkyl groups (preferably C3-C20 cycloalkyl groups, e.g., cyclopropyl, cyclopentyl) , cyclohexyl, 4-methylcyclohexyl, etc. In this invention, when we refer to alkyl groups, it usually means including cycloalkyl groups, but here it is described separately.), aryl groups (preferably aryl groups having 6 to 26 carbon atoms, for example, phenyl, 1-naphthyl, 4-methoxyphenyl, 2-chlorophenyl, 3-methylphenyl, etc.), aralkyl groups (preferably aralkyl groups having 7 to 23 carbon atoms, for example, benzyl, phenethyl, etc.), heterocyclic groups (preferably heterocyclic groups having 2 to 20 carbon atoms, more preferably at least one oxygen atom, a sulfur atom, a nitrogen atom) It is a heterocyclic group having a 5 or 6 membered ring. Heterocyclic groups include aromatic heterocyclic groups and aliphatic heterocyclic groups. For example, tetrahydropyran ring group, tetrahydrofuran ring group, 2-pyridyl, 4-pyridyl, 2-imidazolyl, 2-benzimidazolyl, 2-thiazolyl, 2-oxazolyl, pyrrolidone group, etc.), alkoxy group (preferably an alkoxy group having 1 to 20 carbon atoms, for example, methoxy, ethoxy, isopropyloxy, benzyloxy, etc.), aryloxy group (preferably an aryloxy group having 6 to 26 carbon atoms, for example, phenoxy, 1-naphthyloxy) (Xy, 3-methylphenoxy, 4-methoxyphenoxy, etc.), heterocyclic oxy groups (groups in which an -O- group is bonded to the above heterocyclic group), alkoxycarbonyl groups (preferably alkoxycarbonyl groups having 2 to 20 carbon atoms, for example, ethoxycarbonyl, 2-ethylhexyloxycarbonyl, dodecyloxycarbonyl, etc.), aryloxycarbonyl groups (preferably aryloxycarbonyl groups having 6 to 26 carbon atoms, for example, phenoxycarbonyl, 1-naphthyloxycarbonyl, 3-methylphenoxycarbonyl, 4-methoxyphenoxycarbonyl, etc.),Heterocyclic oxycarbonyl groups (groups in which an -O-CO- group is bonded to the above heterocyclic group), amino groups (preferably amino groups having 0 to 20 carbon atoms, alkylamino groups, arylamino groups, for example, amino(-NH2), N,N-dimethylamino, N,N-diethylamino, N-ethylamino, anilino, etc.), sulfamoyl groups (preferably sulfamoyl groups having 0 to 20 carbon atoms, for example, N,N-dimethylsulfamoyl, N-phenylsulfamoyl, etc.), acyl groups (alkylcarbonyl groups, alkenylcarbonyl groups, alkynylcarbonyl groups, arylcarbonyl groups) The acyl group includes a heterocyclic carbonyl group, preferably a carbon 1 to 20 acyl group, for example, acetyl, propionyl, butyryl, octanoyl, hexadecanoyl, acryloyl, methacryloyl, crotonoyl, benzoyl, naphthoyl, nicotinoyl, etc., and the acyloxy group includes alkylcarbonyloxy groups, alkenylcarbonyloxy groups, alkynylcarbonyloxy groups, and heterocyclic carbonyloxy groups, preferably a carbon 1 to 20 acyloxy group, for example, acetyloxy, propionyloxy, butyryloxy, octanoyloxy, hexadecanoyl (e.g., noyloxy, acryloyloxy, methacryloyloxy, crotonoyloxynicotinoyloxy), allyloxy group (preferably allyloxy group having 7 to 23 carbon atoms, e.g., benzoyloxy, naphthoyloxy), carbamoyl group (preferably carbamoyl group having 1 to 20 carbon atoms, e.g., N,N-dimethylcarbamoyl, N-phenylcarbamoyl), acylamino group (preferably acylamino group having 1 to 20 carbon atoms, e.g., acetylamino, benzoylamino), alkylthio group (preferably alkylthio group having 1 to 20 carbon atoms) Groups, for example, methylthio, ethylthio, isopropylthio, benzylthio, etc.), arylthio groups (preferably arylthio groups having 6 to 26 carbon atoms, for example, phenylthio, 1-naphthylthio, 3-methylphenylthio, 4-methoxyphenylthio, etc.), heterocyclic thio groups (groups in which an -S- group is bonded to the above heterocyclic group), alkylsulfonyl groups (preferably alkylsulfonyl groups having 1 to 20 carbon atoms, for example, methylsulfonyl, ethylsulfonyl, etc.), arylsulfonyl groups (preferably arylsulfonyl groups having 6 to 22 carbon atoms, for example, benzenesulfonyl, etc.),Alkylsilyl groups (preferably alkylsilyl groups having 1 to 20 carbon atoms, e.g., monomethylsilyl, dimethylsilyl, trimethylsilyl, triethylsilyl, etc.), arylsilyl groups (preferably arylsilyl groups having 6 to 42 carbon atoms, e.g., triphenylsilyl, etc.), alkoxysilyl groups (preferably alkoxysilyl groups having 1 to 20 carbon atoms, e.g., monomethoxysilyl, dimethoxysilyl, trimethoxysilyl, triethoxysilyl, etc.), aryloxysilyl groups (preferably aryloxysilyl groups having 6 to 42 carbon atoms, e.g., triphenyloxysilyl, etc.), phosphoryl groups (preferably phosphate groups having 0 to 20 carbon atoms, e.g., -OP(=O)(R, P 2) A phosphonyl group (preferably a phosphonyl group having 0 to 20 carbon atoms, for example, -P(=O)(R P 2) A phosphenyl group (preferably a phosphenyl group having 0 to 20 carbon atoms, for example, -P(R P 2) A phosphonic acid group (preferably a phosphonic acid group having 0 to 20 carbon atoms, for example, -PO(OR P 2) Examples include sulfo groups (sulfonic acid groups), carboxyl groups, hydroxyl groups, sulfanyl groups, cyano groups, and halogen atoms (e.g., fluorine atoms, chlorine atoms, bromine atoms, iodine atoms, etc.). P is a hydrogen atom or a substituent (preferably a group selected from substituent Z). Furthermore, each of the groups listed as substituent Z may be further substituted with the substituent Z mentioned above. The alkyl groups, alkylene groups, alkenyl groups, alkenylene groups, alkynyl groups and / or alkynylene groups mentioned above may be cyclic or linear, and may be linear or branched.
[0125] - Chain polymerization polymer - We will now describe chain polymerization polymers, which are polymers that form the above-mentioned binder. The chain polymer preferably has a component having a functional group selected from the functional group group (a) or a component represented by the formula (1-1) described above, more preferably has a component having the above functional group and a component represented by the formula (1-1), and may also have components other than these components. The chain polymer may not have a component having a functional group selected from the functional group group (a) or a component represented by the formula (1-1) described above, and may be a polymer made of other components.
[0126] Examples of fluorine-containing polymers include polytetrafluoroethylene (PTFE), polyvinylidene difluoride (PVdF), copolymers of polyvinylidene difluoride and hexafluoropropylene (PVdF-HFP), and copolymers of polyvinylidene difluoride, hexafluoropropylene, and tetrafluoroethylene (PVdF-HFP-TFE). In PVdF-HFP, the copolymerization ratio [PVdF:HFP] (mass ratio) of PVdF to HFP is not particularly limited, but 9:1 to 5:5 is preferred, and 9:1 to 7:3 is more preferred from the viewpoint of adhesion. In PVdF-HFP-TFE, the copolymerization ratio [PVdF:HFP:TFE] (mass ratio) of PVdF, HFP, and TFE is not particularly limited, but 20 to 60:10 to 40:5 to 30 is preferred, and 25 to 50:10 to 35:10 to 25 is even more preferred.
[0127] Examples of hydrocarbon polymers include polyethylene, polypropylene, natural rubber, polybutadiene, polyisoprene, polystyrene, polystyrene-butadiene copolymer, styrene-based thermoplastic elastomer, polybutylene, acrylonitrile-butadiene copolymer, or hydrogenated polymers thereof. Examples of styrene-based thermoplastic elastomers or their hydrogenated products are not particularly limited, but include styrene-ethylene-butylene-styrene block copolymer (SEBS), styrene-isoprene-styrene block copolymer (SIS), hydrogenated SIS, styrene-butadiene-styrene block copolymer (SBS), hydrogenated SBS, styrene-ethylene-ethylene-propylene-styrene block copolymer (SEEPS), styrene-ethylene-propylene-styrene block copolymer (SEPS), styrene-butadiene rubber (SBR), hydrogenated styrene-butadiene rubber (HSBR), and random copolymers corresponding to the above block copolymers such as SEBS. In the present invention, hydrocarbon polymers that do not have unsaturated groups (e.g., 1,2-butadiene components) bonded to the main chain are preferred in that they can suppress the formation of chemical crosslinks.
[0128] Examples of vinyl polymers include polymers containing, for example, 50 mol% or more of vinyl monomers other than (meth)acrylic compounds (M1). Examples of vinyl monomers include vinyl compounds described later. Specifically, examples of vinyl polymers include polyvinyl alcohol, polyvinyl acetal, polyvinyl acetate, or copolymers containing these. This vinyl polymer may also preferably contain components derived from a (meth)acrylic compound (M1) that forms the (meth)acrylic polymer described later, in addition to components derived from vinyl monomers. The content of components derived from vinyl monomers is preferably the same as the content of components derived from (meth)acrylic compound (M1) in the (meth)acrylic polymer. The content of components derived from (meth)acrylic compound (M1) is not particularly limited as long as it is less than 50 mol% in the polymer, but is preferably 0 to 30 mol%.
[0129] As the (meth)acrylic polymer, a polymer obtained by copolymerizing at least one (meth)acrylic compound (M1) selected from (meth)acrylic acid compounds, (meth)acrylic acid ester compounds, (meth)acrylamide compounds, and (meth)acrylonitrile compounds as another component is preferred. A (meth)acrylic polymer consisting of a copolymer of (meth)acrylic compound (M1) and another polymerizable compound (M2) is also preferred. The other polymerizable compound (M2) is not particularly limited and includes vinyl compounds such as styrene compounds, vinylnaphthalene compounds, vinylcarbazole compounds, allyl compounds, vinyl ether compounds, vinyl ester compounds, dialkyl itaconate compounds, and unsaturated carboxylic acid anhydrides, as well as fluorinated products thereof. As an example of a vinyl compound, "vinyl monomers" described in Japanese Patent Application Publication No. 2015-88486 can be mentioned. The (meth)acrylic compound (M1) and other polymerizable compounds (M2) may have substituents. The substituents are not particularly limited as long as they are not functional groups included in the above-mentioned functional group group (a), and preferably include groups selected from substituent Z. The content of other polymerizable compounds (M2) in the (meth)acrylic polymer is not particularly limited, but can be, for example, 50 mol% or less.
[0130] As the (meth)acrylic compound (M1) and vinyl compound (M2) that lead to the constituent components of the (meth)acrylic polymer and vinyl polymer, compounds represented by the following formula (b-1) are preferred. This compound is different from the constituent components having the functional groups included in the above-mentioned functional group group (a) and the compounds that lead to the constituent components represented by the above formula (1-1).
[0131] [ka]
[0132] In the formula, R 1represents a hydrogen atom, a hydroxyl group, a cyano group, a halogen atom, an alkyl group (preferably with 1 to 24 carbon atoms, more preferably with 1 to 12 carbon atoms, and particularly preferably with 1 to 6 carbon atoms), an alkenyl group (preferably with 2 to 24 carbon atoms, more preferably with 2 to 12 carbon atoms, and particularly preferably with 2 to 6 carbon atoms), an alkynyl group (preferably with 2 to 24 carbon atoms, more preferably with 2 to 12 carbon atoms, and particularly preferably with 2 to 6 carbon atoms), or an aryl group (preferably with 6 to 22 carbon atoms, and more preferably with 6 to 14 carbon atoms). Among these, a hydrogen atom or an alkyl group is preferred, and a hydrogen atom or a methyl group is more preferred.
[0133] R 2 R represents a hydrogen atom or substituent. 2 The substituents that can be chosen are not particularly limited, but include alkyl groups (branched chains are also acceptable, but straight chains are preferred), alkenyl groups (2 to 12 carbon atoms are preferred, 2 to 6 carbon atoms are more preferred, and 2 or 3 carbon atoms are particularly preferred), aryl groups (6 to 22 carbon atoms are preferred, and 6 to 14 carbon atoms are more preferred), aralkyl groups (7 to 23 carbon atoms are preferred, and 7 to 15 carbon atoms are more preferred), and cyano groups. The alkyl group preferably has 1 to 3 carbon atoms. The alkyl group may have, for example, a substituent Z other than the functional group included in the above functional group group (a).
[0134] L 1 The linking group is not particularly limited, but may include, for example, an alkylene group having 1 to 6 carbon atoms (preferably 1 to 3), an alkenylene group having 2 to 6 carbon atoms (preferably 2 to 3), an arylene group having 6 to 24 carbon atoms (preferably 6 to 10), an oxygen atom, a sulfur atom, or an imino group (-NR). N -:R N As mentioned above, examples include carbonyl groups, phosphate linking groups (-OP(OH)(O)-O-), phosphonic acid linking groups (-P(OH)(O)-O-), or groups related to combinations thereof, such as -CO-O- groups and -CO-N(R N )-group(R Nis as described above.) is preferred. The above linking group may have any substituent. The number of atoms constituting the linking group and the number of linking atoms are as described later. Examples of the optional substituent include the aforementioned substituent Z, for example, an alkyl group or a halogen atom and the like.
[0135] n is 0 or 1, and 1 is preferred. Provided that, -(L 1 ) n -R 2 represents one type of substituent (e.g., an alkyl group), n is set to 0, and R 2 is defined as a substituent (an alkyl group).
[0136] Preferred examples of the above (meth)acrylic compound (M1) also include compounds represented by the following formula (b-2) or (b-3). These compounds are different from the compound that leads to the constituent component having the functional group included in the aforementioned functional group group (a) and the constituent component represented by the above formula (1-1).
[0137]
Chemical Formula
[0138] R 1 and n have the same definitions as in the above formula (b-1). R 3 has the same definition as R 2 . L 2 is a linking group, and has the same definition as the above L 1 . L 3 is a linking group, and has the same definition as the above L 1 , and is preferably an alkylene group having 1 to 6 (preferably 1 to 3) carbon atoms. m is an integer of 1 to 200, preferably an integer of 1 to 100, and more preferably an integer of 1 to 50.
[0139] In the above formulas (b-1) to (b-3), among the carbon atoms forming the polymerizable group, the carbon atom that is R 1Carbon atoms that are not bonded are represented as unsubstituted carbon atoms (H2C=), but they may have substituents. There are no particular restrictions on substituents, but for example, R 1 The above groups can be considered as such. Furthermore, in formulas (b-1) to (b-3), groups that may take substituents, such as alkyl groups, aryl groups, alkylene groups, and arylene groups, may have substituents to the extent that they do not impair the effects of the present invention. The substituents may be any substituents other than the functional groups selected from the functional group group (a), for example, groups selected from substituent Z described later, specifically halogen atoms, etc.
[0140] The (meth)acrylic polymer preferably has components having a functional group selected from the functional group group (a) described above, or components represented by the formula (1-1) described above, and may have components derived from the (meth)acrylic compound (M1), components derived from the vinyl compound (M2), and other components copolymerizable with compounds that lead to these components. Having components represented by the formula (1-1) described above and components having a functional group selected from the functional group group (a) among the (meth)acrylic compound (M1) is preferable in terms of dispersion stability and binding properties.
[0141] The chain polymer (each component and raw material compound) may have substituents. The substituents are not particularly limited, and preferably include groups selected from the substituent Z described above, and groups other than the functional groups included in the functional group group (a) described above are preferred.
[0142] The content of the constituent components in the (meth)acrylic polymer is not particularly limited and can be appropriately selected and set to the following ranges, for example. The content of the constituent components represented by formula (1-1) above and the constituent components having functional groups selected from the functional group group (a) is as described above. The content of the constituent component derived from the (meth)acrylic compound (M1) in the (meth)acrylic polymer is not particularly limited and can be 100 mol%, but is preferably 1 to 90 mol%, more preferably 10 to 80 mol%, and particularly preferably 20 to 70 mol%. The content of the vinyl compound (M2) component in the (meth)acrylic polymer is not particularly limited, but is preferably 1 to 50 mol%, more preferably 10 to 50 mol%, and particularly preferably 20 to 50 mol%.
[0143] The chain polymer (each component and raw material compound) may have substituents. The substituent is not particularly limited as long as it is a functional group other than those included in the above-mentioned functional group group (a), and preferably a group selected from substituent Z.
[0144] Chain polymers can be synthesized by selecting raw material compounds and polymerizing them using known methods. There are no particular limitations on the method of incorporating functional groups. Examples include copolymerizing a compound having a functional group selected from functional group (a), using a polymerization initiator or chain transfer agent having (or producing) the above-mentioned functional group, utilizing polymer reactions, ene reactions or ene-thiol reactions to double bonds (for example, formed by the dehydrofluoridation reaction of VDF components in the case of fluoropolymers), or ATRP (Atom Transfer Radical Polymerization) polymerization using a copper catalyst. In addition, functional groups can also be introduced by using functional groups present in the main chain, side chains, or terminals of the polymer as reaction sites. For example, a functional group selected from functional group (a) can be introduced by using a compound having a functional group and reacting it with carboxylic acid anhydride groups in the polymer chain in various ways.
[0145] Specific examples of polymers forming polymer binder A or B include those synthesized in the examples, as shown below, but the present invention is not limited to these. In each specific example, the number in the lower right corner of the constituent component indicates the content in the polymer, and the unit is mole percent.
[0146] [ka]
[0147] Polymer binders A and B can be selected from suitable polymers as long as the solubility and adsorption rates are met. For example, the polymer forming polymer binder A is preferably a polymer having at least one of the following bonds in its main chain: urethane bond, urea bond, amide bond, imide bond, and ester bond, and more preferably a polymer having urethane bond in its main chain. The polymer forming polymer binder B is preferably a polymer having a polymerization chain of carbon-carbon double bonds in its main chain, and more preferably a (meth)acrylic polymer. The combination of the polymer forming polymer binder A and the polymer forming polymer binder B can be determined as appropriate, and the same type of polymer can be used for each, but it is preferable to use different types of polymers (for example, polymers with different chemical structures in their main chains), and specifically, preferred combinations of preferred polymers are preferred.
[0148] (Polymer binders A and B, or the physical properties or characteristics of the polymers forming these binders) Polymer binder A or B, or the polymer forming polymer binder A or B, preferably has the following physical properties or characteristics. The mass-average molecular weight of the polymer forming polymer binder A is not particularly limited, but for example, it is preferably 15,000 or more, more preferably 30,000 or more, and even more preferably 50,000 or more. As an upper limit, 5,000,000 or less is substantial, but 4,000,000 or less is preferred, 3,000,000 or less is more preferred, and it can also be 200,000 or less. On the other hand, the mass-average molecular weight of the polymer forming polymer binder B is not particularly limited, but for example, it is preferably 15,000 or more, more preferably 30,000 or more, and even more preferably 50,000 or more. As an upper limit, 5,000,000 or less is substantial, but 4,000,000 or less is preferred, 3,000,000 or less is more preferred, and it can also be 200,000 or less. The mass-average molecular weight of the polymer can be adjusted as appropriate by changing the type and content of polymerization initiators, polymerization time, polymerization temperature, etc.
[0149] - Measurement of molecular weight - In this invention, unless otherwise specified, the molecular weight of polymers, polymer chains, polymerization chains, and macromonomers refers to the mass-average molecular weight or number-average molecular weight on a standard polystyrene basis, measured by gel permeation chromatography (GPC). The basic measurement method is the method set according to condition 1 or condition 2 (preferred) below. However, depending on the type of polymer, polymer chain, or macromonomer, an appropriate eluent may be selected and used as appropriate. (Condition 1) Column: Two TOSOH TSKgel Super AWM-H columns (product name, manufactured by Tosoh Corporation) are connected together. Carrier: 10 mM LiBr / N-methylpyrrolidone Measurement temperature: 40℃ Carrier flow rate: 1.0 ml / min Sample concentration: 0.1% by mass Detector: RI (refractive index) detector (Condition 2) Column: A column connected with TOSOH TSKgel Super HZM-H, TOSOH TSKgel Super HZ4000, and TOSOH TSKgel Super HZ2000 (all are trade names, manufactured by Tosoh Corporation) is used. Carrier: Tetrahydrofuran Measurement temperature: 40°C Carrier flow rate: 1.0 ml / min Sample concentration: 0.1 mass% Detector: RI (refractive index) detector
[0150] The adsorption rates of polymer binders A and B to the conductive auxiliary agent described later are not particularly limited. Since the content of the conductive auxiliary agent relative to the active material (AC) and the inorganic solid electrolyte (SE) is small, its influence on dispersion properties and binding properties is small, and the adsorption rate to the conductive auxiliary agent does not need to be set to a specific range.
[0151] The water concentration of the polymer is preferably 100 ppm (mass basis) or less. In addition, polymer binders A and B may be those obtained by crystallizing and drying the polymer, or the polymer solution may be used as it is. The polymers forming polymer binders A and B are preferably amorphous. In the present invention, that a polymer is "amorphous" typically means that no endothermic peak due to crystal melting is observed when measured at the glass transition temperature. The polymers forming polymer binders A and B may be non-crosslinked polymers or crosslinked polymers. Further, when crosslinking of the polymer proceeds by heating or application of voltage, the molecular weight may be larger than the above molecular weight. Preferably, the polymer has a mass average molecular weight in the above range at the start of use of the all-solid secondary battery.
[0152] The total content of the polymer binder (PB) in the electrode composition is not particularly limited and is appropriately set, and for example, can be 0.3 to 3.0 mass% in 100 mass% of the solid content. The total content of polymer binders A and B in the electrode composition is appropriately set according to the content of each polymer binder, and in order to achieve both low resistance and dispersion and binding properties, it can be, for example, 0.5 to 2.0% by mass, preferably 0.5 to 1.5% by mass, and more preferably 0.5 to 1.0% by mass, based on 100% by mass of solids. The content of polymer binder A and polymer binder B in the electrode composition is not particularly limited and can be set as appropriate. The content of both may be set, for example, taking into consideration the dispersion characteristics and binding properties of polymer binder A or B. In this case, the content can be 2.0 parts by mass or less, preferably 0.3 to 1.5 parts by mass, and more preferably 0.5 to 1.0 parts by mass, per 100 parts by mass of the active material (AC) or inorganic solid electrolyte (SE) contained in the electrode composition. The content of polymer binder A in the electrode composition can be set higher than that of polymer binder B in order to adsorb the active material (AC) which is generally contained in large quantities in the electrode composition. Specifically, in order to achieve both low resistance and dispersion characteristics and binding properties (especially of polymer binder A), it is preferable that the content is 0.1 to 3.0% by mass, more preferably 0.3 to 3.0% by mass, even more preferably 0.5 to 1.5% by mass, and particularly preferable 0.5 to 1.0% by mass, based on 100% by mass of solid content. Furthermore, the content of polymer binder B in the electrode composition is specifically, in order to achieve both low resistance and dispersion characteristics and binding properties (especially of polymer binder B), for example, it is preferable that the content is 0.1 to 2.0% by mass, more preferably 0.2 to 1.5% by mass, and even more preferably 0.2 to 1.0% by mass, based on 100% by mass of solid content. The difference between the content of polymer binder A and the content of polymer binder B (content of polymer binder A - content of polymer binder B), and the ratio of the content of polymer binder A to the content of polymer binder B (content of polymer binder A / content of polymer binder B), are not particularly limited and are set appropriately according to the content of the active material (AC) or inorganic solid electrolyte (SE), etc. If the electrode composition contains two or more polymer binders A or B, the above-mentioned content of polymer binders A or B shall be the total content.
[0153] (Other polymer binders) The electrode composition of the present invention may contain one or more polymer binders other than polymer binders A and B (referred to as "other polymer binders"). Examples of other polymer binders include, with regard to adsorption rate, low-adsorption binders having an adsorption rate of less than 20% for both the active material (AC) and the inorganic solid electrolyte (SE) in the dispersion medium (D), and with regard to solubility in the dispersion medium (D), particulate binders that are insoluble in the dispersion medium (D). Other polymers that form polymer binders can be any polymer used as a binder for all-solid-state secondary batteries, as long as they satisfy the adsorption rate or solubility requirements. Examples include the sequential polymers and chain polymers mentioned above. Examples of particulate binders include those described in Japanese Patent Publication No. 2015-088486, International Publication No. 2017 / 145894, and International Publication No. 2018 / 020827. The particle size of the particulate binder (measured by the same method as for inorganic solid electrolytes) is not particularly limited and can be, for example, 1 to 1000 nm. The content of other polymer binders is not particularly limited and can be set appropriately within a range that does not impair the effects of the present invention, for example, it can be 1% by mass or less.
[0154] In the present invention, at a solid content of 100% by mass, the mass ratio of the total mass of inorganic solid electrolyte (SE) and active material (AC) to the total mass of polymer binder (PB) [(mass of SE + mass of AC) / (total mass of polymer binder (PB))] is preferably in the range of 1,000 to 1. This ratio is more preferably 500 to 2, and even more preferably 100 to 10.
[0155] <Dispersion medium (D)> The electrode composition of the present invention contains a dispersion medium (D) that disperses or dissolves each of the above components. Such dispersion medium (D) can be any organic compound that is liquid in the environment of use, for example, various organic solvents, specifically alcohol compounds, ether compounds, amide compounds, amine compounds, ketone compounds, aromatic compounds, aliphatic compounds, nitrile compounds, ester compounds, etc. The dispersion medium (D) may be either a nonpolar dispersion medium (hydrophobic dispersion medium) or a polar dispersion medium (hydrophilic dispersion medium), but a nonpolar dispersion medium is preferred because it can exhibit excellent dispersion characteristics. A nonpolar dispersion medium generally refers to a material with low affinity for water, and in the present invention, examples include ester compounds, ketone compounds, ether compounds, aromatic compounds, aliphatic compounds, and the like.
[0156] Examples of alcohol compounds include methyl alcohol, ethyl alcohol, 1-propyl alcohol, 2-propyl alcohol, 2-butanol, ethylene glycol, propylene glycol, glycerin, 1,6-hexanediol, cyclohexanediol, sorbitol, xylitol, 2-methyl-2,4-pentanediol, 1,3-butanediol, and 1,4-butanediol.
[0157] Examples of ether compounds include alkylene glycols (diethylene glycol, triethylene glycol, polyethylene glycol, dipropylene glycol, etc.), alkylene glycol monoalkyl ethers (ethylene glycol monomethyl ether, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, diethylene glycol monomethyl ether, dipropylene glycol monomethyl ether, tripropylene glycol monomethyl ether, diethylene glycol monobutyl ether, etc.), alkylene glycol dialkyl ethers (ethylene glycol dimethyl ether, etc.), dialkyl ethers (dimethyl ether, diethyl ether, diisopropyl ether, dibutyl ether, etc.), and cyclic ethers (tetrahydrofuran, dioxane (including 1,2-, 1,3-, and 1,4- isomers), etc.).
[0158] Examples of amide compounds include N,N-dimethylformamide, N-methyl-2-pyrrolidone, 2-pyrrolidinone, 1,3-dimethyl-2-imidazolidinone, ε-caprolactam, formamide, N-methylformamide, acetamide, N-methylacetamide, N,N-dimethylacetamide, N-methylpropanamide, and hexamethylphosphoric triamide.
[0159] Examples of amine compounds include triethylamine, diisopropylethylamine, and tributylamine. Examples of ketone compounds include acetone, methyl ethyl ketone, methyl isobutyl ketone (MIBK), cyclopentanone, cyclohexanone, cycloheptanone, dipropyl ketone, dibutyl ketone, diisopropyl ketone, diisobutyl ketone (DIBK), isobutylpropyl ketone, sec-butylpropyl ketone, pentylpropyl ketone, and butylpropyl ketone. Examples of aromatic compounds include benzene, toluene, xylene, and perfluorotoluene. Examples of aliphatic compounds include hexane, heptane, octane, nonane, decane, dodecane, cyclohexane, methylcyclohexane, ethylcyclohexane, cycloheptane, cyclooctane, decalin, paraffin, gasoline, naphtha, kerosene, and diesel fuel. Examples of nitrile compounds include acetonitrile, propionitrile, and isobutyronitrile. Examples of ester compounds include ethyl acetate, propyl acetate, butyl acetate, ethyl butyrate, propyl butyrate, isopropyl butyrate, butyl butyrate, isobutyl butyrate, butyl pentanoate, pentyl pentanoate, ethyl isobutyrate, propyl isobutyrate, isopropyl isobutyrate, isobutyl isobutyrate, propyl pivalate, isopropyl pivalate, butyl pivalate, and isobutyl pivalate.
[0160] In the present invention, ether compounds, ketone compounds, aromatic compounds, aliphatic compounds, and ester compounds are preferred, and ester compounds, ketone compounds, or ether compounds are more preferred.
[0161] The number of carbon atoms in the compound constituting the dispersion medium is not particularly limited, but is preferably 2 to 30, more preferably 4 to 20, even more preferably 6 to 15, and particularly preferably 7 to 12.
[0162] The boiling point of the dispersion medium at normal pressure (1 atmosphere) is not particularly limited, but is preferably 90°C or higher, and more preferably 120°C or higher. The upper limit is preferably 230°C or lower, and more preferably 200°C or lower.
[0163] The dispersion medium (D) contained in the electrode composition of the present invention may be one type or two or more types. The content of the dispersion medium (D) in the electrode composition is not particularly limited and can be set as appropriate. For example, 20 to 80% by mass is preferred, 30 to 70% by mass is more preferred, and 40 to 60% by mass is particularly preferred.
[0164] <Conductive additive (CA)> The electrode composition of the present invention preferably contains a conductive additive (CA). There are no particular restrictions on the conductive additive, and any commonly known conductive additive can be used. For example, it may be an electronically conductive material such as graphite, artificial graphite, or other graphites; carbon blacks such as acetylene black, Ketjen black, or furnace black; amorphous carbon such as needle coke; carbon fibers such as vapor-grown carbon fibers or carbon nanotubes; or carbonaceous materials such as graphene or fullerene. It may also be a metal powder or metal fiber such as copper or nickel, or a conductive polymer such as polyaniline, polypyrrole, polythiophene, polyacetylene, or polyphenylene derivatives. In this invention, when an active material and a conductive additive are used in combination, the conductive additive is defined as one which does not function as an active material because, when the battery is charged and discharged, insertion and release of ions of metals belonging to Group 1 or Group 2 of the periodic table (preferably Li ions) does not occur. Therefore, among the conductive additives, those which can function as an active material in the active material layer when the battery is charged and discharged are classified as active materials, not conductive additives. Whether or not a conductive additive functions as an active material when the battery is charged and discharged is not unique, but is determined by the combination with the active material.
[0165] The conductive additive contained in the electrode composition of the present invention is preferably in particulate form. The shape of the particles is not particularly limited and may be flattened, amorphous, etc., but spherical or granular is preferred. When the conductive additive is in particulate form, the particle size (volume average particle size) of the conductive additive is not particularly limited, but for example, 0.02 to 1.0 μm is preferred, and 0.03 to 0.5 μm is more preferred. The particle size of the conductive additive can be adjusted in the same manner as the particle size of the inorganic solid electrolyte, and the measurement method can also be the same as that for the particle size of the inorganic solid electrolyte. The electrode composition of the present invention may contain one or more conductive additives. The content of the conductive additive in the electrode composition is not particularly limited and can be determined as appropriate. For example, it is preferably 10% by mass or less, and more preferably 1.0 to 5.0% by mass, based on 100% by mass of solid content.
[0166] <Lithium salts> The electrode composition of the present invention may also contain a lithium salt (supporting electrolyte). The lithium salt is preferably one commonly used in this type of product, and is not particularly limited; for example, the lithium salt described in paragraphs 0082 to 0085 of Japanese Patent Application Publication No. 2015-088486 is preferred. When the electrode composition of the present invention contains a lithium salt, the lithium salt content is preferably 0.1 parts by mass or more, more preferably 5 parts by mass or more, per 100 parts by mass of the inorganic solid electrolyte. The upper limit is preferably 50 parts by mass or less, and more preferably 20 parts by mass or less.
[0167] <Dispersant> The electrode composition of the present invention does not need to contain any dispersants other than the polymer binder (PB), as the polymer binder (PB), particularly polymer binders A and B, also function as a dispersant. If the electrode composition contains a dispersant other than the polymer binder (PB), then a dispersant commonly used in all-solid-state secondary batteries can be appropriately selected and used. Generally, compounds intended for particle adsorption and steric repulsion and / or electrostatic repulsion are preferably used.
[0168] <Other additives> The electrode composition of the present invention may optionally contain, in addition to the above-mentioned components, ionic liquids, thickeners, crosslinking agents (such as those that undergo crosslinking reactions by radical polymerization, condensation polymerization, or ring-opening polymerization), polymerization initiators (such as those that generate acids or radicals by heat or light), defoaming agents, leveling agents, dehydrating agents, antioxidants, etc. The ionic liquid is included to further improve ionic conductivity, and known ionic liquids can be used without particular limitation.
[0169] (Preparation of electrode composition) The electrode composition of the present invention can be prepared by conventional methods. For example, an inorganic solid electrolyte (SE), an active material (AC), a polymer binder (PB), and a dispersion medium (D), and optionally a conductive additive (CA), a lithium salt, and any other components can be mixed, for example, in a commonly used mixer, to prepare a mixture, preferably a slurry. The method of mixing the above components is not particularly limited; the components may be mixed all at once or sequentially. In the all-at-once mixing method, the adsorption rate of polymer binders A and B is AC and A SE This method is preferable in terms of work efficiency when the difference is large. In the present invention, it is preferable to prepare the electrode composition by mixing the above components using the electrode composition preparation method of the present invention, which has the following steps. This method allows polymer binder A to be preferentially adsorbed onto the active material (AC), and polymer binder B to be preferentially adsorbed onto the inorganic solid electrolyte (SE), and as a result, the dispersion characteristics and binding properties of the active material (AC) and inorganic solid electrolyte (SE) can be further improved. Active material composition preparation process: A process for preparing an active material composition containing an active material (AC), a polymer binder A, and a dispersion medium (D). Solid electrolyte composition preparation process: A process for preparing a solid electrolyte composition containing an inorganic solid electrolyte (SE), a polymer binder B, and a dispersion medium (D). Electrode composition preparation process: A step of mixing the prepared active material composition with the solid electrolyte composition.
[0170] - Active material composition preparation process - In the active material composition preparation step, the active material (AC), polymer binder A, and dispersion medium (D) are (pre-)mixed to prepare the active material composition. This step allows the polymer binder A to be preferentially adsorbed onto the active material (AC) (avoiding adsorption with the inorganic solid electrolyte (SE)), and a mixture (slurry) in which the active material (AC) is adsorbed (bound) with polymer binder A is obtained. This step is preferably performed in the absence of the inorganic solid electrolyte (SE) and / or polymer binder B in order to enhance the preferential adsorption of polymer binder A onto the active material (AC). Here, "absence" includes the presence of the inorganic solid electrolyte (SE) and polymer binder B in a range that does not impair the effects of the present invention, for example, in an amount of 5% by mass or less relative to the solid content of the electrode composition. In this process, the amount of each component used is set appropriately, taking into consideration the content of each component in the target electrode composition. Typically, the mixing amount (content) of the active material (AC) and polymer binder A is set to the same range as the content of each component in 100% by mass of solids in the electrode composition. That is, the mixing ratio of the active material (AC) and polymer binder A is not particularly limited, but it is generally preferable in terms of work efficiency to set it to the mixing ratio of the active material (AC) and polymer binder A in the electrode composition. The amount of dispersion medium (D) used is appropriately set considering the content of dispersion medium (D) in the electrode composition, the amount of dispersion medium (D) used in the solid electrolyte composition preparation step, etc., but it is preferable to use an amount that dissolves polymer binder A. For example, focusing on the solid content concentration of the obtained active material composition, it can be 20 to 85% by mass, and it is preferable to set it to 40 to 80% by mass. On the other hand, focusing on the content of dispersion medium (D) in the electrode composition, when its content is set to 100% by mass, it can be 0.1 to 70% by mass, and it is preferable to set it to 0.5 to 60% by mass.
[0171] The mixing method and mixing conditions in this process are not particularly limited and can be set as appropriate. For example, the mixing order of each component may be all at once or sequentially. Furthermore, the mixing method can be carried out using known mixers such as ball mills, bead mills, planetary mixers, blade mixers, roll mills, kneaders, disc mills, revolving mixers, and narrow-gap dispersers. Mixing conditions can be, for example, a mixing temperature of 10 to 60°C, a rotation speed of 10 to 700 rpm (rotations per minute) for revolving mixers, and a mixing time of 5 minutes to 5 hours. When using a ball mill as the mixer, it is preferable to set the rotation speed to 50 to 700 rpm and the mixing time to 5 minutes to 24 hours, preferably 5 to 60 minutes, at the above mixing temperature. The mixing atmosphere can be any of the following: air, dry air (dew point below -20°C), or in an inert gas (e.g., argon, helium, or nitrogen). Since inorganic solid electrolytes readily react with moisture, mixing is preferably carried out in dry air or an inert gas. Furthermore, the mixing process in this step can be carried out in multiple stages.
[0172] - Solid electrolyte composition preparation process - In the solid electrolyte composition preparation step, the inorganic solid electrolyte (SE), polymer binder B, and dispersion medium (D) are (pre-)mixed to prepare the inorganic solid electrolyte composition. This step allows the polymer binder B to be preferentially adsorbed onto the inorganic solid electrolyte (SE) (avoiding adsorption with the active material (AC)), and a mixture (slurry) in which the inorganic solid electrolyte (SE) is adsorbed (bound) with polymer binder B is obtained. This step is preferably performed in the absence of the active material (AC) and / or polymer binder A in order to enhance the preferential adsorption of polymer binder B onto the inorganic solid electrolyte (SE). Here, "absence" includes the presence of the active material (AC) and polymer binder A in a content of 10% by mass or less relative to the solid content of the electrode composition, within a range that does not impair the effects of the present invention.
[0173] In this process, the amount of each component used is set appropriately, taking into consideration the content of each component in the target electrode composition. Typically, the mixing amount (content) of the inorganic solid electrolyte (SE) and polymer binder B is set to the same range as the content of each component in 100% by mass of solid content in the electrode composition. That is, the mixing ratio of inorganic solid electrolyte (SE) and polymer binder B is not particularly limited, but it is generally preferable in terms of work efficiency to set it to the mixing ratio of inorganic solid electrolyte (SE) and polymer binder B in the electrode composition. The amount of dispersion medium (D) used is set appropriately considering the content of dispersion medium (D) in the electrode composition, the amount of dispersion medium (D) used in the active material composition preparation step, etc., but it is preferable to use an amount that dissolves polymer binder B. For example, focusing on the solid content concentration of the resulting solid electrolyte composition, it can be 20 to 85% by mass, and it is preferable to set it to 40 to 80% by mass. On the other hand, focusing on the content of dispersion medium (D) in the electrode composition, when the content is set to 100% by mass, it can be 0.1 to 70% by mass, and it is preferable to set it to 0.5 to 60% by mass. It is preferable that the total amount of dispersion medium (D) used in the active material composition preparation step and the solid electrolyte composition preparation step is set to the same range as the content of dispersion medium (D) in the electrode composition.
[0174] The mixing method and conditions in this process are not particularly limited and can be set as appropriate. For example, the mixing method and conditions used in the active material composition preparation process can be applied. The mixing method and conditions used in this process may be the same as or different from those used in the active material composition preparation process.
[0175] - Electrode composition preparation process - In the method for preparing the electrode composition of the present invention, a step is performed to prepare the electrode composition by mixing the active material composition obtained in each of the above steps with the solid electrolyte composition. This makes it possible to highly disperse each component in the dispersion medium (D) while maintaining the adsorption state of the active material (AC) and polymer binder A in the active material composition, and the adsorption state of the inorganic solid electrolyte (SE) and polymer binder B in the solid electrolyte composition. In this process, the mixing ratio of the active material composition and the solid electrolyte composition is not particularly limited, but it is preferable to mix them in a ratio such that the content of each active material (AC), inorganic solid electrolyte (SE), polymer binder A, and polymer binder B is the same as the content of each in the electrode composition. Regarding the dispersion medium (D), any deficiency relative to the content in the electrode composition can be added in this process, or any excess can be concentrated. The mixing method and conditions in this process are not particularly limited and can be set as appropriate; for example, the mixing method and conditions used in the active material composition preparation process can be applied. The mixing method and conditions used in this process may be the same as or different from those used in the active material composition preparation process or the solid electrolyte composition preparation process. In the electrode composition preparation method of the present invention, the active material composition obtained in the active material composition preparation step and the solid electrolyte composition obtained in the solid electrolyte composition preparation step are dispersed in the dispersion medium (D) with the active material (AC) or inorganic solid electrolyte (SE) adsorbed onto polymer binder A or polymer binder B. Therefore, the electrode composition preparation step does not need to be performed immediately after the completion of the above two composition preparation steps, and can be performed with a time interval as long as the dispersibility of both compositions is not impaired.
[0176] In the method for preparing the electrode composition of the present invention, when a conductive additive (CA), lithium salt, dispersant, and other additives are used, these components may be mixed in any of the steps. It is preferable that these components be mixed in the electrode composition preparation step, as this does not inhibit the preferential adsorption of the active material (AC) or inorganic solid electrolyte (SE) to polymer binder A or polymer binder B. The amount of these components mixed is usually preferably set to the same range as the content in the electrode composition.
[0177] [Electrode sheets for all-solid-state secondary batteries] The electrode sheet for all-solid-state secondary batteries of the present invention (sometimes simply referred to as an electrode sheet) is a sheet-like molded body capable of forming an active material layer or electrode (a laminate of an active material layer and a current collector) of an all-solid-state secondary battery, and includes various embodiments depending on its application.
[0178] The electrode sheet of the present invention may be any electrode sheet having an active material layer composed of the electrode composition of the present invention as described above. The active material layer may be formed on a substrate (current collector), or it may be a sheet without a substrate, formed solely from the active material layer. This electrode sheet is usually a sheet having a substrate (current collector) and an active material layer, but embodiments having a substrate (current collector), an active material layer, and a solid electrolyte layer in that order are also included, as well as embodiments having a substrate (current collector), an active material layer, a solid electrolyte layer, and an active material layer in that order. Furthermore, the electrode sheet may have other layers in addition to the above-mentioned layers. Examples of other layers include a protective layer (release sheet), a coating layer, and so on.
[0179] The substrate is not particularly limited as long as it can support the active material layer, and examples include sheets (plate-like bodies) of materials such as current collectors, organic materials, and inorganic materials, as described later. Examples of organic materials include various polymers, specifically polyethylene terephthalate, polypropylene, polyethylene, and cellulose. Examples of inorganic materials include glass and ceramics.
[0180] At least one of the active material layers of the electrode sheet is formed from the electrode composition of the present invention. The content of each component in the active material layer formed from the electrode composition of the present invention is not particularly limited, but preferably it is the same as the content of each component in the solid content of the electrode composition of the present invention. The thickness of each layer constituting the electrode sheet of the present invention is the same as the thickness of each layer described later in the all-solid-state secondary battery. In the present invention, each layer constituting the sheet for the all-solid-state secondary battery may be a single-layer structure or a multi-layer structure. If the solid electrolyte layer or active material layer is not formed with the electrode composition of the present invention, it will be formed with a conventional constituent layer forming material.
[0181] The electrode sheet of the present invention has an active material layer formed from the electrode composition of the present invention, and has a low-resistance active material layer in which solid particles are firmly bound together. Therefore, by using the electrode sheet for all-solid-state secondary batteries of the present invention as the active material layer of an all-solid-state secondary battery, it is possible to realize an all-solid-state secondary battery that exhibits low resistance and excellent rate characteristics. In particular, an electrode sheet for all-solid-state secondary batteries in which the active material layer is formed on a current collector exhibits strong adhesion between the active material layer and the current collector, and further improvement in rate characteristics can be achieved. Thus, the electrode sheet for all-solid-state secondary batteries of the present invention is suitably used as a sheet-like member that forms the active material layer, preferably the electrode, of an all-solid-state secondary battery (it is incorporated as an active material layer or electrode).
[0182] [Manufacturing method for electrode sheets for all-solid-state secondary batteries] The method for manufacturing the electrode sheet for an all-solid-state secondary battery of the present invention is not particularly limited, and it can be manufactured by forming an active material layer using the electrode composition of the present invention, preferably an electrode composition prepared by the method for preparing the electrode composition of the present invention. For example, one method is to form a layer (coated and dried layer) made of the electrode composition by forming a film (coated and dried layer) of the electrode composition of the present invention on the surface of a substrate (may be via other layers). This makes it possible to produce an electrode sheet for an all-solid-state secondary battery having a substrate and a coated and dried layer. In particular, if a current collector is used as the substrate, the adhesion between the current collector and the active material layer (coated and dried layer) can be strengthened. Here, the coated and dried layer refers to a layer formed by coating the electrode composition of the present invention and drying the dispersion medium (i.e., a layer made using the electrode composition of the present invention, and consisting of a composition obtained by removing the dispersion medium from the electrode composition of the present invention). The active material layer and the coated and dried layer may contain residual dispersion medium as long as it does not impair the effects of the present invention, and the residual amount can be, for example, 3% by mass or less in the coated and dried layer. In the method for manufacturing electrode sheets for all-solid-state secondary batteries of the present invention, each step such as coating and drying will be explained in the method for manufacturing all-solid-state secondary batteries described below.
[0183] In this way, an electrode sheet for an all-solid-state secondary battery can be manufactured having an active material layer consisting of a coated and dried layer, or an active material layer produced by appropriately pressurizing the coated and dried layer. The pressurizing conditions and other details will be explained later in the section on the manufacturing method of the all-solid-state secondary battery. Furthermore, in the method for manufacturing electrode sheets for all-solid-state secondary batteries of the present invention, the substrate, protective layer (especially the release sheet), etc., can also be peeled off.
[0184] [All-solid-state secondary battery] The all-solid-state secondary battery of the present invention comprises a positive electrode active material layer, a negative electrode active material layer facing the positive electrode active material layer, and a solid electrolyte layer disposed between the positive electrode active material layer and the negative electrode active material layer. The all-solid-state secondary battery of the present invention is not particularly limited in its other configurations, as long as it has a solid electrolyte layer between the positive electrode active material layer and the negative electrode active material layer, and for example, known configurations relating to all-solid-state secondary batteries can be adopted. In a preferred all-solid-state secondary battery, the positive electrode active material layer has a positive electrode current collector laminated on the surface opposite to the solid electrolyte layer to constitute the positive electrode, and the negative electrode active material layer has a negative electrode current collector laminated on the surface opposite to the solid electrolyte layer to constitute the negative electrode. In the present invention, each constituent layer (including current collectors, etc.) constituting the all-solid-state secondary battery may have a single-layer structure or a multi-layer structure.
[0185] In the all-solid-state secondary battery of the present invention, at least one layer of the negative electrode active material layer and the positive electrode active material layer is formed of the electrode composition of the present invention, and it is preferable that at least the positive electrode active material layer is formed of the electrode composition of the present invention. It is also a preferred embodiment that both the negative electrode active material layer and the positive electrode active material layer are formed of the electrode composition of the present invention. Furthermore, with respect to the negative electrode (a laminate of negative electrode current collectors and positive electrode current collectors) and the positive electrode (a laminate of positive electrode current collectors and positive electrode current collectors), it is preferable that either one, preferably the positive electrode, is formed of the electrode sheet for all-solid-state secondary batteries of the present invention, and it is also a preferred embodiment that both are formed of the electrode sheet for all-solid-state secondary batteries of the present invention. In the present invention, forming the active material layer of an all-solid-state secondary battery with the electrode composition of the present invention includes embodiments in which the constituent layers are formed with the electrode sheet for all-solid-state secondary batteries of the present invention (provided that if there are layers other than the active material layer formed of the electrode composition of the present invention, these layers are removed from the sheet). The active material layer formed with the electrode composition of the present invention preferably contains the same types of components and their content as those in the solid content of the electrode composition of the present invention. If the active material layer is not formed using the electrode composition of the present invention, the active material layer and the solid electrolyte layer can be manufactured using known materials. In the present invention, each constituent layer (including current collectors, etc.) constituting the all-solid-state secondary battery may have a single-layer structure or a multi-layer structure.
[0186] <Positive electrode active material layer and negative electrode active material layer> The thickness of the negative electrode active material layer and the positive electrode active material layer are not particularly limited. Considering the dimensions of a typical all-solid-state secondary battery, the thickness of each layer is preferably 10 to 1,000 μm, and more preferably 20 μm or more and less than 500 μm. In the all-solid-state secondary battery of the present invention, it is even more preferable that the thickness of at least one of the positive electrode active material layer and the negative electrode active material layer is 50 μm or more and less than 500 μm.
[0187] <Solid electrolyte layer> The solid electrolyte layer is formed using a known material capable of forming a solid electrolyte layer for an all-solid-state secondary battery. Its thickness is not particularly limited, but is preferably 10 to 1,000 μm, and more preferably 20 μm or more and less than 500 μm.
[0188] <Current collector> The positive electrode active material layer and the negative electrode active material layer are preferably each provided with a current collector on the side opposite to the solid electrolyte layer. Electron conductors are preferred as such positive electrode and negative electrode current collectors. In this invention, either the positive electrode current collector or the negative electrode current collector, or both together, may be simply referred to as the current collector. As materials for forming the positive electrode current collector, in addition to aluminum, aluminum alloys, stainless steel, nickel, and titanium, materials in which carbon, nickel, titanium, or silver has been treated on the surface of aluminum or stainless steel (with a thin film formed) are preferred, and among these, aluminum and aluminum alloys are more preferred. As materials for forming the negative electrode current collector, in addition to aluminum, copper, copper alloys, stainless steel, nickel, and titanium, materials in which carbon, nickel, titanium, or silver has been treated on the surface of aluminum, copper, copper alloys, or stainless steel are preferred, and aluminum, copper, copper alloys, and stainless steel are more preferred.
[0189] While current collectors are typically made of film sheets, other forms such as nets, punched materials, laths, porous materials, foams, and molded fiber bundles can also be used. The thickness of the current collector is not particularly limited, but 1 to 500 μm is preferred. Furthermore, it is preferable to create an uneven surface on the current collector surface through surface treatment.
[0190] <Other configurations> In the present invention, functional layers or components may be appropriately interposed or arranged between or outside each layer of the negative electrode current collector, negative electrode active material layer, solid electrolyte layer, positive electrode active material layer, and positive electrode current collector.
[0191] <Enclosure> The all-solid-state secondary battery of the present invention may be used as an all-solid-state secondary battery with the above structure in its current form, depending on the application. However, to form a dry cell, it is preferable to enclose it in a suitable housing. The housing may be made of metal or resin (plastic). When using a metal housing, examples include aluminum alloy or stainless steel. It is preferable that the metal housing be divided into a positive electrode housing and a negative electrode housing, and electrically connected to the positive electrode current collector and the negative electrode current collector, respectively. It is preferable that the positive electrode housing and the negative electrode housing are joined together and integrated via a gasket to prevent short circuits.
[0192] A preferred embodiment of the all-solid-state secondary battery of the present invention will be described below with reference to Figure 1, but the present invention is not limited thereto.
[0193] Figure 1 is a schematic cross-sectional view showing an all-solid-state secondary battery (lithium-ion secondary battery) according to a preferred embodiment of the present invention. In this embodiment, the all-solid-state secondary battery 10 has, when viewed from the negative electrode side, a negative electrode current collector 1, a negative electrode active material layer 2, a solid electrolyte layer 3, a positive electrode active material layer 4, and a positive electrode current collector 5 in this order. Each layer is in contact with the others and has an adjacent structure. By adopting such a structure, during charging, electrons (e - ) is supplied, and lithium ions (Li +) accumulates. On the other hand, during discharge, lithium ions (Li) accumulated on the negative electrode are released. + The discharge is returned to the positive electrode side, and electrons are supplied to the working part 6. In the illustrated example, a light bulb is used as a model for the working part 6, and it is designed to light up when the discharge occurs.
[0194] When an all-solid-state secondary battery having the layer configuration shown in Figure 1 is placed in a 2032-type coin case, this all-solid-state secondary battery is sometimes referred to as an all-solid-state secondary battery laminate, and the battery made by placing this all-solid-state secondary battery laminate in a 2032-type coin case is sometimes referred to as a (coin-type) all-solid-state secondary battery.
[0195] (solid electrolyte layer) The solid electrolyte layer can be any of those used in conventional all-solid-state secondary batteries without any particular limitations. This solid electrolyte layer contains an inorganic solid electrolyte having the conductivity of metal ions belonging to Group 1 or Group 2 of the periodic table, and optionally any of the above-mentioned components, and usually does not contain an active material.
[0196] (Positive electrode active material layer and negative electrode active material layer) In the all-solid-state secondary battery 10, both the positive electrode active material layer and the negative electrode active material layer are formed from the electrode composition of the present invention. Preferably, the positive electrode, formed by laminating the positive electrode active material layer and the positive electrode current collector, and the negative electrode, formed by laminating the negative electrode active material layer and the negative electrode current collector, are formed from the electrode sheet of the present invention to which the current collector is applied as a substrate. The positive electrode active material layer contains an inorganic solid electrolyte having conductivity of metal ions belonging to Group 1 or Group 2 of the periodic table, a positive electrode active material, polymer binders A and B, and any of the above-mentioned components, etc., to the extent that they do not impair the effects of the present invention. The negative electrode active material layer contains an inorganic solid electrolyte having conductivity of metal ions belonging to Group 1 or Group 2 of the periodic table, a negative electrode active material, polymer binders A and B, and any of the above-mentioned components, etc., within a range that does not impair the effects of the present invention. In the all-solid-state secondary battery 10, the negative electrode active material layer can be a lithium metal layer. Examples of the lithium metal layer include a layer formed by depositing or molding lithium metal powder, lithium foil, and lithium vapor-deposited film. The thickness of the lithium metal layer can be, for example, 1 to 500 μm, regardless of the above-mentioned thickness of the negative electrode active material layer.
[0197] Each component contained in the positive electrode active material layer 4, the solid electrolyte layer 3, and the negative electrode active material layer 2, particularly the inorganic solid electrolyte, the conductive additive, and the polymer binder, may be of the same type or different types.
[0198] In the present invention, by forming the active material layer with the electrode composition of the present invention, an all-solid-state secondary battery with low resistance and excellent rate characteristics can be realized.
[0199] (Current collector) The positive electrode current collector 5 and the negative electrode current collector 1 are as described above.
[0200] In the above-described all-solid-state secondary battery 10, if it has constituent layers other than those formed with the electrode composition of the present invention, layers formed with known constituent layer forming materials can also be applied. Furthermore, each layer may consist of a single layer or multiple layers.
[0201] [Manufacturing of all-solid-state rechargeable batteries] All-solid-state secondary batteries can be manufactured by conventional methods. Specifically, all-solid-state secondary batteries can be manufactured by forming at least one active material layer using the electrode composition of the present invention, and forming a solid electrolyte layer, and optionally the other active material layer or electrodes, using known materials.
[0202] The all-solid-state secondary battery of the present invention can be manufactured by a method (method for manufacturing an electrode sheet for an all-solid-state secondary battery of the present invention) that includes a step of applying the electrode composition of the present invention to the surface of a substrate (for example, a metal foil that will serve as a current collector) and drying it to form a coating film (film formation). For example, a positive electrode sheet for an all-solid-state secondary battery is fabricated by applying an electrode composition containing a positive electrode active material as the positive electrode material (positive electrode composition) onto a metal foil, which serves as the positive electrode current collector, to form a positive electrode active material layer. Next, an inorganic solid electrolyte-containing composition for forming a solid electrolyte layer is applied on top of this positive electrode active material layer to form a solid electrolyte layer. Furthermore, an electrode composition containing a negative electrode active material is applied on top of the solid electrolyte layer as the negative electrode material (negative electrode composition) to form a negative electrode active material layer. By stacking a negative electrode current collector (metal foil) on top of the negative electrode active material layer, an all-solid-state secondary battery can be obtained in which a solid electrolyte layer is sandwiched between the positive electrode active material layer and the negative electrode active material layer. This can also be enclosed in a housing to create a desired all-solid-state secondary battery. Furthermore, by reversing the formation method of each layer, a negative electrode active material layer, a solid electrolyte layer, and a positive electrode active material layer can be formed on a negative electrode current collector, and a positive electrode current collector can be stacked on top to manufacture an all-solid-state secondary battery.
[0203] Another method is as follows: A positive electrode sheet for an all-solid-state secondary battery is manufactured as described above. A negative electrode active material layer is formed by coating a metal foil, which is the negative electrode current collector, with an electrode composition containing a negative electrode active material (negative electrode composition) to form a negative electrode active material layer, thereby manufacturing a negative electrode sheet for an all-solid-state secondary battery. Next, a solid electrolyte layer is formed on the active material layer of either of these sheets as described above. Furthermore, the other of the positive electrode sheet and negative electrode sheet for an all-solid-state secondary battery is laminated on the solid electrolyte layer so that the solid electrolyte layer and the active material layer are in contact. In this way, an all-solid-state secondary battery can be manufactured. Another method is as follows: A positive electrode sheet and a negative electrode sheet for an all-solid-state secondary battery are prepared as described above. Separately, an inorganic solid electrolyte-containing composition is applied to a substrate to prepare a solid electrolyte sheet for an all-solid-state secondary battery consisting of a solid electrolyte layer. Furthermore, the positive electrode sheet and the negative electrode sheet for an all-solid-state secondary battery are laminated so as to sandwich the solid electrolyte layer peeled from the substrate. In this way, an all-solid-state secondary battery can be manufactured.
[0204] Furthermore, a positive electrode sheet or negative electrode sheet for an all-solid-state secondary battery, and a solid electrolyte sheet for an all-solid-state secondary battery are manufactured as described above. Next, the positive electrode sheet or negative electrode sheet and the solid electrolyte sheet are stacked on top of each other with the positive electrode active material layer or negative electrode active material layer and the solid electrolyte layer in contact, and then pressurized. In this way, the solid electrolyte layer is transferred to the positive electrode sheet or negative electrode sheet for an all-solid-state secondary battery. After that, the solid electrolyte layer from which the substrate of the solid electrolyte sheet has been peeled off is stacked on top of the negative electrode sheet or positive electrode sheet for an all-solid-state secondary battery (with the negative electrode active material layer or positive electrode active material layer in contact with the solid electrolyte layer), and pressurized. In this way, an all-solid-state secondary battery can be manufactured. The pressurizing method and pressurizing conditions in this method are not particularly limited, and the methods and pressurizing conditions described in the pressurizing process described later can be applied.
[0205] The active material layer, etc., can be formed, for example, by pressurizing an electrode composition, etc., on a substrate or active material layer under the pressurizing conditions described later, or a sheet molded body of the active material can be used. In the above manufacturing method, the electrode composition of the present invention may be used for either the positive electrode composition or the negative electrode composition, or it may be used for both the positive electrode composition and the negative electrode composition. When forming the active material layer with a composition other than the electrode composition of the present invention, examples of such materials include commonly used compositions. Furthermore, instead of forming the negative electrode active material layer during the manufacture of the all-solid-state secondary battery, the negative electrode active material layer can also be formed by combining ions of metals belonging to Group 1 or 2 of the periodic table, which have accumulated on the negative electrode current collector during initialization or charging during use as described later, with electrons, and depositing them as metals on the negative electrode current collector, etc.
[0206] <Formation of each layer (film formation)> The application method for each composition is not particularly limited and can be selected as appropriate. Examples of wet application methods include coating (preferably wet coating), spray coating, spin coating, dip coating, slit coating, stripe coating, and bar coating. The coated composition is preferably subjected to a drying treatment (heat treatment). The drying treatment may be performed after each individual coating of the composition, or after multi-layer coating. The drying temperature is not particularly limited as long as the dispersion medium can be removed, and is set appropriately according to the boiling point of the dispersion medium, etc. For example, the lower limit of the drying temperature is preferably 30°C or higher, more preferably 60°C or higher, and even more preferably 80°C or higher. The upper limit is preferably 300°C or lower, more preferably 250°C or lower, and even more preferably 200°C or lower. By heating within this temperature range, the dispersion medium can be removed, resulting in a solid state (coated dried layer). This is also preferable because it avoids excessively high temperatures and prevents damage to each component of the all-solid-state secondary battery. As a result, the all-solid-state secondary battery can exhibit excellent overall performance, good coating suitability (adhesion), and good ionic conductivity even without pressure. When the electrode composition of the present invention is applied and dried as described above, variations in the contact state can be suppressed, solid particles can be firmly bound together, and a low-resistance applied and dried layer can be formed.
[0207] It is preferable to apply pressure to each layer or to the entire solid-state battery after applying each composition, stacking the constituent layers, or after manufacturing the all-solid-state secondary battery. Examples of pressurizing methods include hydraulic cylinder presses. The pressurizing pressure is not particularly limited, but is generally preferably in the range of 5 to 1500 MPa. Furthermore, each applied composition may be heated simultaneously with pressurization. The heating temperature is not particularly limited, but is generally in the range of 30 to 300°C. Pressing can also be done at a temperature higher than the glass transition temperature of the inorganic solid electrolyte. It can also be done at a temperature higher than the glass transition temperature of the polymer constituting the polymer binder. However, generally, the temperature should not exceed the melting point of the polymer. Pressurization may be performed after the coating solvent or dispersion medium has been dried beforehand, or it may be performed while the solvent or dispersion medium is still present. The compositions may be applied simultaneously, or the application, drying, and pressing may be performed simultaneously and / or sequentially. They may also be applied to separate substrates and then laminated by transfer.
[0208] The atmosphere used in the film formation method (coating, drying, and pressurizing under heating) is not particularly limited and may be any of the following: open air, dry air (dew point below -20°C), or in an inert gas (e.g., argon, helium, or nitrogen). The pressing time can be short (e.g., within a few hours) and high pressure, or long (more than a day) and moderate pressure. For applications other than electrode sheets for solid-state rechargeable batteries, such as solid-state rechargeable batteries themselves, a restraining device for solid-state batteries (e.g., screw tightening pressure) can be used to maintain a moderate pressure. The press pressure may be uniform or varied across the sheet surface or other areas being pressed. The press pressure can be varied according to the area or film thickness of the part being pressed. It is also possible to apply different pressures to the same area in stages. The pressed surface may be smooth or roughened.
[0209] <Initialization> It is preferable to initialize the all-solid-state secondary battery manufactured as described above after manufacturing or before use. Initialization is not particularly limited and can be performed, for example, by performing the initial charge and discharge under increased press pressure, and then releasing the pressure until it reaches the general operating pressure of the all-solid-state secondary battery.
[0210] [Applications of all-solid-state rechargeable batteries] The all-solid-state secondary battery of the present invention can be applied to a variety of uses. There are no particular limitations on the applications, but examples of applications when mounted on electronic devices include laptop computers, pen-input computers, mobile computers, e-book players, mobile phones, cordless phone handsets, pagers, handheld terminals, portable fax machines, portable copiers, portable printers, headphone stereos, video cameras, LCD televisions, handheld vacuum cleaners, portable CDs, MiniDiscs, electric shavers, transceivers, electronic organizers, calculators, memory cards, portable tape recorders, radios, and backup power supplies. Other consumer applications include automobiles (electric vehicles, etc.), electric vehicles, motors, lighting fixtures, toys, game consoles, road conditioners, clocks, strobes, cameras, and medical devices (pacemakers, hearing aids, shoulder massagers, etc.). Furthermore, it can be used for various military and space applications. It can also be combined with solar cells. [Examples]
[0211] The present invention will be described in more detail below based on examples, but the present invention is not to be construed as being limited thereto. In the following examples, "parts" and "%" representing composition are by mass unless otherwise specified. In the present invention, "room temperature" means 25°C.
[0212] 1. Polymer synthesis Polymers S1 to S15, shown in the following chemical formulas, were synthesized as follows.
[0213] [Synthesis Example S1: Synthesis of Polymer S1 and Preparation of Binder Solution S1] 46.1 g of NISSO-PB GI-3000 (trade name, manufactured by Nippon Soda Co., Ltd.) was added to a 200 mL three-necked flask and dissolved in 64 g of butyl butyrate (manufactured by Tokyo Chemical Industry Co., Ltd.). 3.9 g of dicyclohexylmethane-4,4'-diisocyanate (manufactured by Tokyo Chemical Industry Co., Ltd.) was added to this solution and stirred at 80°C until uniformly dissolved. 0.1 g of Neostan U-600 (trade name, manufactured by Nitto Chemical Co., Ltd.) was added to the resulting solution and stirred at 80°C for 10 hours to synthesize polymer S1 (polyurethane), obtaining a polymer binder solution S1 (concentration 40% by mass) consisting of polymer S1.
[0214] [Synthesis Example S2: Synthesis of Polymer S2 and Preparation of Binder Solution S2] In synthesis example S1, polymer S2 (polyurethane) was synthesized in the same manner as in synthesis example S1, except that compounds were used to derive each component so that polymer S2 had the composition (types and content of constituent components) shown in Table 1, and a polymer binder solution S2 consisting of polymer S2 was obtained.
[0215] [Synthesis Example S3: Synthesis of Polymer S3 and Preparation of Binder Solution S3] In a 100 mL volumetric flask, 2.9 g of 2-hydroxyethyl acrylate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), 19.1 g of dodecyl methacrylate (manufactured by Tokyo Chemical Industry Co., Ltd.), and 0.3 g of polymerization initiator V-601 (trade name, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were added and dissolved in 36 g of butyl butyrate to prepare a monomer solution. Next, 12 g of butyl butyrate was added to a 300 mL three-necked flask and stirred at 80°C, to which the above monomer solution was added dropwise over 2 hours. After the dropwise addition was complete, the temperature was raised to 90°C and stirred for 2 hours to synthesize polymer S3 (acrylic polymer), and a polymer binder solution S3 (concentration 30% by mass) consisting of polymer S3 was obtained.
[0216] [Synthesis Example S4: Synthesis of Polymer S4 and Preparation of Binder Solution S4] In synthesis example S3, polymer S4 (acrylic polymer) was synthesized in the same manner as in synthesis example S3, except that compounds were used to derive each component so that polymer S4 had the composition (types and content of constituent components) shown in Table 1, and a polymer binder solution S4 consisting of polymer S4 was obtained.
[0217] [Synthesis Examples S5 and S6: Synthesis of polymers S5 and S6 and preparation of binder solutions S5 and S6] In synthesis example S3, polymers S5 and S6 (acrylic polymers) were synthesized in the same manner as in synthesis example S3, except that compounds were used to derive each component so that polymers S5 and S6 had the compositions (types and content of constituent components) shown in Table 1, respectively. This yielded polymer binder solutions S5 and S6, respectively, composed of each polymer.
[0218] [Synthesis Example S7: Synthesis of Polymer S7 and Preparation of Binder Dispersion S7] 200 g of heptane was poured into a 1 L three-necked flask equipped with a reflux condenser and a gas inlet stopcock, and nitrogen gas was introduced at a flow rate of 200 mL / min for 10 minutes, after which the temperature was raised to 80°C. A solution prepared in a separate container (a mixture of 177 g of ethyl acrylate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), 13 g of acrylic acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), 100 g (solid content) of macromonomer AB-6 (trade name, manufactured by Toagosei Co., Ltd.), and 2.0 g of polymerization initiator V-601 (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.)) was added dropwise over 2 hours, and the mixture was then stirred at 80°C for 2 hours. An additional 1.0 g of V-601 was added to the resulting mixture, and the mixture was stirred at 90°C for 2 hours. Dilution of the resulting solution with heptane yielded a dispersion of polymer S7 consisting of a particulate binder (concentration 10% by mass, particle size 150 nm).
[0219] [Synthesis Examples S8-S14: Synthesis of polymers S8-S14 and preparation of binder solutions S8-S14] In synthesis example S3, polymers S8 to S13 (acrylic polymers) and polymer S14 (vinyl polymer) were synthesized in the same manner as in synthesis example S3, except that compounds were used to derive each component so that polymers S8 to S14 had the compositions (types and content of constituent components) shown in Table 1. Solutions S8 to S14 of polymer binders, each composed of these polymers, were obtained.
[0220] [Synthesis Example S15: Synthesis of Polymer S15 and Preparation of Binder Solution S15] In synthesis example S1, polymer S15 (polyurethane) was synthesized in the same manner as in synthesis example S1, except that compounds were used to derive each component so that polymer S15 had the composition (types and content of constituent components) shown in Table 1, and a polymer binder solution S15 consisting of polymer S15 was obtained.
[0221] [Synthesis Example S16: Synthesis of Polymer S16 and Preparation of Binder Dispersion S16] In synthesis example S7, polymer S16 was synthesized in the same manner as in synthesis example S7, except that compounds were used to derive each component so that polymer S16 had the composition (types and content of constituent components) shown in Table 1, thereby obtaining a dispersion S16 of particulate binder (concentration 10% by mass, particle size 120 nm) consisting of polymer S16.
[0222] The synthesized polymers S1-S3, S5, S6, and S8-S15 are shown below. Note that polymer S4 is identical to polymer S3 except for the content of its constituent components, so its chemical formula is omitted. The numbers in the lower right corner of each component indicate the content (mol%).
[0223] [ka]
[0224] [ka]
[0225] Table 1 shows the composition of each synthesized polymer (binder), the presence or absence of functional groups, the mass-average molecular weight measured by the method described above, and the form of the binder in the composition (soluble or insoluble), which will be described later. Note that the unit of content of each component is "mol%", but this is omitted in Table 1. The form of the binder was determined by measuring the solubility in the dispersion medium (butyl butyrate) used in each composition using the method described above. Furthermore, for each polymer binder prepared, the adsorption rate A of the inorganic solid electrolyte (SE) (LPS with an average particle size of 2.5 μm synthesized in Synthesis Example A) used in the preparation of the cathode composition described later was also determined. SE , and adsorption rate A for the active material (AC) (NMC111) AC The difference in adsorption rate (A) was measured using the method described above. AC and A SE The absolute value of the difference between the two was calculated. On the other hand, the adsorption rate A of the prepared polymer binders S1 to S4 to the inorganic solid electrolyte (SE) (LPS with an average particle size of 2.5 μm synthesized in synthesis example A) used in the preparation of the negative electrode composition described later was calculated. SE , and adsorption rate A for active material (AC)(LTO) AC The difference in adsorption rate (A) was measured using the method described above. AC and A SE The absolute value of the difference between the two values was calculated. The results obtained are shown in Table 1. Note that for polymer binders S1 to S4, see "A" in Table 1. AC In the column, "Adsorption rate A for positive electrode active material" AC " and "Adsorption rate A for negative electrode active material AC " and " are listed together separated by " / ", and in the "Difference" column, "Adsorption rate A for positive electrode active material" AC Adsorption rate A to inorganic solid electrolytes SE "The difference between" and "Adsorption rate A for the negative electrode active material" AC Adsorption rate A to inorganic solid electrolytes SEThe difference between and is shown together separated by a " / ". Furthermore, the adsorption rate A was calculated using the active material (AC), inorganic solid electrolyte (SE), polymer binder A and polymer binder B, and the dispersion medium (D) used in the preparation of the positive electrode composition or negative electrode composition, which were extracted from the active material of the positive electrode sheet or negative electrode sheet obtained in the <Preparation of positive electrode sheet for all-solid-state secondary battery> described later. SE and adsorption rate A AC Similar values were obtained when the measurement was taken.
[0226] [Table 1]
[0227] <Abbreviations in the table> In the table, a "-" in the component column indicates that the corresponding component is not present. H12MDI: Dicyclohexylmethane 4,4'-diisocyanate (manufactured by Tokyo Chemical Industry Co., Ltd.) HMDI: Hexamethylene diisocyanate (manufactured by Tokyo Chemical Industry Co., Ltd.) GI-3000: NISSO-PB GI-3000 (product name, hydroxyl-hydrogenated polybutadiene at both ends, number average molecular weight 3100, manufactured by Nippon Soda Co., Ltd.) HEA: 2-hydroxyethyl acrylate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) LA: Dodecyl acrylate (manufactured by Tokyo Chemical Industry Co., Ltd.) OA: Octyl acrylate (manufactured by Tokyo Chemical Industry Co., Ltd.) EA: Ethyl acrylate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) AA: Acrylic acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) AB-6: Polybutyl acrylate with methacryloyl terminal functional groups (number average molecular weight 6000, manufactured by Toagosei Co., Ltd.) Phosmer M: Methacrylate ester containing a phosphate group (trade name, manufactured by Unichemical Co., Ltd.) DMAEM: N,N-dimethylaminoethyl (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) NMI: N-methylmaleimide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) EDA: Ethylenediamine (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) St: Styrene (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) Unless otherwise specified, all other components were compounds manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.
[0228] 2. Synthesis of sulfide-based inorganic solid electrolytes [Synthesis Example A] The sulfide-based inorganic solid electrolyte was synthesized with reference to non-patent literature: T. Ohtomo, A. Hayashi, M. Tatsumisago, Y. Tsuchida, S. Hama, K. Kawamoto, Journal of Power Sources, 233, (2013), pp231-235, and A. Hayashi, S. Hama, H. Morimoto, M. Tatsumisago, T. Minami, Chem. Lett., (2001), pp872-873. Specifically, 2.42 g of lithium sulfide (Li2S, Aldrich, purity >99.98%) and 3.90 g of phosphorus pentasulfide (P2S5, Aldrich, purity >99%) were weighed out in a glove box under an argon atmosphere (dew point -70°C), placed in an agate mortar, and mixed for 5 minutes using an agate pestle. The mixing ratio of Li2S to P2S5 was 75:25 molar ratio. Next, 66 g of 5 mm diameter zirconia beads were placed in a 45 mL zirconia container (manufactured by Fritsch), and the entire amount of the lithium sulfide and phosphorus pentasulfide mixture was added. The container was then sealed under an argon atmosphere. The container was placed in a planetary ball mill P-7 (trade name, manufactured by Fritsch), and mechanical milling (atomization) was performed at a temperature of 25 °C and a rotation speed of 510 rpm for 20 hours to obtain 6.20 g of yellow powder sulfide-based inorganic solid electrolyte (Li / P / S glass, hereinafter sometimes referred to as LPS). The particle size (volume average particle size) of this LPS was 8 μm. The obtained LPS was wet-dispersed under the following conditions to adjust the particle size of the LPS. Specifically, 160 zirconia beads with a diameter of 5 mm were placed in a 45 mL zirconia container (manufactured by Fritsch), and 4.0 g of synthesized LPS and 6.0 g of diisopropyl ketone as an organic solvent were added. Then, the container was set in a planetary ball mill P-7, and wet dispersion was performed at 250 rpm for 30 minutes to obtain LPS with a particle size (volume average particle size) of 2.5 μm.
[0229] [Example 1] <Preparation of positive electrode composition (slurry) S-1> A positive electrode composition (solid content concentration 65% by mass) S-1 was prepared by mixing 70 parts by mass of NMC111 (lithium nickel manganese cobalt oxide, particle size 5 μm, manufactured by Aldrich) as the positive electrode active material (AC), 27 parts by mass of LPS (particle size 2.5 μm) obtained in the above synthesis example A as the inorganic solid electrolyte (SE), 2.3 parts by mass of acetylene black (particle size 0.1 μm, manufactured by Denka) as the conductive additive (CA), 0.7 parts by mass (on a solid content basis) of polymer binder solution S1 as polymer binder A, 0.27 parts by mass (on a solid content basis) of polymer binder solution S3 as polymer binder B, and a dispersion medium (D) in the following steps 1, 2, and 3.
[0230] (Step 1: Active material composition preparation step) 20 g of 3 mm diameter zirconia beads were added to a 45 mL zirconia container (manufactured by Fritsch). Then, 70 parts by mass of the above-mentioned positive electrode active material, 0.7 parts by mass (in terms of solid content) of binder solution S1, and butyl butyrate as a dispersion medium were added to adjust the solid content concentration to 70% by mass. After that, this container was set in a planetary ball mill P-7 (trade name, manufactured by Fritsch) and stirred for 30 minutes at a temperature of 25°C and a rotation speed of 100 rpm to obtain active material composition S1-1 with a solid content concentration of 70% by mass. (Step 2: Solid electrolyte composition preparation step) 20 g of 3 mm diameter zirconia beads were added to a 45 mL zirconia container (manufactured by Fritsch). Then, 27 parts by mass of inorganic solid electrolyte, 0.27 parts by mass of binder solution S3 (in terms of solid content), and butyl butyrate as a dispersion medium were added to adjust the solid content concentration to 60% by mass. Subsequently, this container was placed in a planetary ball mill P-7 and stirred for 30 minutes at a temperature of 25°C and a rotation speed of 100 rpm to obtain solid electrolyte composition S1-2 with a solid content concentration of 60% by mass. (Step 3: Electrode composition preparation step) 20 g of 3 mm diameter zirconia beads were added to a 45 mL zirconia container (manufactured by Fritsch). Then, the entire amount of the active material composition S1-1 obtained in step 1, the entire amount of the solid electrolyte composition S1-2 obtained in step 2, 2.3 parts by mass of acetylene black, and the dispersion medium necessary to adjust the solid content concentration of the resulting cathode composition to 65% by mass were added. After that, this container was set in a planetary ball mill P-7 and stirred for 30 minutes at a temperature of 25°C and a rotation speed of 100 rpm to obtain cathode composition S-1 (solid content concentration 65% by mass).
[0231] <Preparation of positive electrode compositions (slurries) S-2 to S-24> In the preparation of positive electrode composition (slurry) S-1, positive electrode compositions (slurries) S-2 to S-24 were prepared in the same manner as positive electrode composition (slurry) S-1, except that the type or content of polymer binder A, the type or content of polymer binder B, and the content of the conductive additive were changed as shown in Table 2-1.
[0232] <Preparation of negative electrode compositions (slurries) T-1 to T-4> The negative electrode compositions (slurries) T-1 to T-4 were prepared in the same manner as the preparation of the positive electrode composition (slurry) S-1, except that the type or content of polymer binder A, the type or content of polymer binder B, and the type and content of active material and conductive additive were changed as shown in Table 2-2.
[0233] In Tables 2-1 and 2-2 (collectively referred to as Table 2), the adsorption rate A ACand adsorption rate A SE For each case, the difference (absolute value) between polymer binder A and polymer binder B is calculated and shown in Table 2. Polymer binders S5-S7 and S16 do not correspond to polymer binders A and B as defined in this invention. However, for convenience, in the positive electrode compositions S-3-S-10 and S-24 shown in Table 2, the polymer binder used in step 1 is listed in the "Binder A" column, and the polymer binder used in step 2 is listed in the "Binder B" column. In Table 2, the content of each component is shown as the amount (parts by mass) used in the preparation of each composition, but the units are omitted in the table.
[0234] [Table 2-1]
[0235] [Table 2-2]
[0236] <Abbreviations in the table> NMC111: LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (Aldrich) LPS: LPS with a particle size of 2.5 μm synthesized in synthesis example A. AB: Acetylene black (Denka) LTO: Lithium titanate (Aldrich)
[0237] <Fabrication of positive electrode sheets for all-solid-state secondary batteries> Each of the positive electrode compositions S-1 to S-24 obtained above was applied onto a 20 μm thick aluminum foil using a Baker-type applicator (product name: SA-201, manufactured by Tester Sangyo Co., Ltd.), and the positive electrode composition was dried (dispersion medium removed) by heating at 100°C for 1 hour. In this way, a positive electrode active material layer was formed on the aluminum foil, and positive electrode sheets P-1 to P-24 for all-solid-state secondary batteries were fabricated. The thickness of the positive electrode active material layer was 110 μm.
[0238] <Fabrication of negative electrode sheets for all-solid-state secondary batteries> Each of the negative electrode compositions T-1 to T-4 obtained above was applied onto a 20 μm thick stainless steel (SUS) foil using a Baker-type applicator (product name: SA-201, manufactured by Tester Sangyo Co., Ltd.), and the negative electrode composition was dried (dispersion medium removed) by heating at 100°C for 1 hour. In this way, a negative electrode active material layer was formed on the SUS foil, and negative electrode sheets N-1 to N-4 for all-solid-state secondary batteries were fabricated. The thickness of the negative electrode active material layer was 100 μm.
[0239] <Manufacturing of all-solid-state rechargeable batteries> Each of the fabricated positive electrode sheets P-1 to P-24 or negative electrode sheets N-1 to N-4 for solid-state secondary batteries was punched out into a 10 mm diameter disc shape and placed in a polyethylene terephthalate (PET) cylinder with an inner diameter of 10 mm. 30 mg of LPS with a particle size of 2.5 μm obtained in synthesis example A was placed on the positive electrode active material layer side of each cylinder, and a 10 mm diameter stainless steel rod (SUS rod) was inserted through the openings at both ends of the cylinder. The current collector side of each positive electrode sheet and the LPS were pressurized with a pressure of 350 MPa using the SUS rod. The SUS rod on the LPS side was temporarily removed, and a 9 mm diameter disc-shaped In sheet (thickness 20 μm) and a 9 mm diameter disc-shaped Li sheet (thickness 20 μm) were inserted in that order on top of the LPS in the cylinder. The removed SUS rod was reinserted into the cylinder and fixed under a pressure of 50 MPa. In this manner, all-solid-state secondary batteries (positive electrode half-cells) No. C-1 to C-24, having the configuration of aluminum foil (thickness 20 μm) - positive electrode active material layer (thickness 70 μm) - solid electrolyte layer (thickness 200 μm) - negative electrode active material layer (In / Li sheet, thickness 30 μm), and all-solid-state secondary batteries (negative electrode half-cells) No. C-25 to C-28, having the configuration of SUS foil (thickness 20 μm) - negative electrode active material layer (thickness 70 μm) - solid electrolyte layer (thickness 200 μm) - positive electrode active material layer (In / Li sheet, thickness 30 μm), were manufactured.
[0240] Each manufactured composition, sheet, and all-solid-state secondary battery was evaluated as described below, and the results are shown in Tables 3-1 and 3-2 (collectively referred to as Table 3).
[0241] <Evaluation 1: Dispersion stability test> Each of the prepared compositions (slurries) S-1 to S-24 and T-1 to T-4 was placed in a glass test tube with a diameter of 10 mm and a height of 4 cm to a height of 4 cm, and allowed to stand at 25°C for 3 hours. The ratio of solid content in the 1 cm portion of the slurry liquid surface before and after standing was calculated. Specifically, immediately after standing, the liquid from the slurry surface down to 1 cm was taken out and heated and dried in an aluminum cup at 120°C for 3 hours. The mass of the solid content in the cup afterward was measured to determine the solid content before and after standing. The solid content ratio [W2 / W1] of the solid content W2 after standing to the solid content W1 before standing was then determined. The ease of settling of the active material (AC) and inorganic solid electrolyte (SE) was evaluated as a measure of the dispersion stability of the solid electrolyte composition, based on which of the following evaluation criteria the solid content ratio [W2 / W1] falls into. In this test, the closer the solid content ratio [W2 / W1] is to 1, the better the dispersion stability, and an evaluation of "B" or higher is considered a passing level. Furthermore, electrode compositions S-1, S-2, S-11 to S-23 and T-1 and T-2 exhibited excellent dispersibility immediately after preparation. On the other hand, the solid content ratios [W2 / W1] of electrode compositions S-3 and S-4 were 0.58 and 0.61, respectively. - Evaluation Criteria - S: 0.95 ≤ [W2 / W1] ≤ 1.0 A: 0.90 ≤ [W2 / W1] < 0.95 B: 0.8 ≤ [W2 / W1] < 0.90 C: [W2 / W1]<0.8
[0242] <Evaluation 2: Bonding Test (Vibration Test)> Each of the fabricated positive electrode sheets P-1 to P-24 and negative electrode sheets N-1 to N-4 for all-solid-state secondary batteries was punched out into a 10mm diameter disc shape. These disc-shaped test pieces were placed without fixing at the bottom of a screw-cap tube (Maruemu Co., Ltd., No. 6, 30mL capacity, 30mm diameter x 65mm total length) with the active material layer facing upwards, and then sealed inside. This screw-cap tube was fixed to a test tube mixer (product name: Delta Mixer Se-40, Taitec Co., Ltd.), and vibrated for 30 seconds with the amplitude set to 2800 revolutions / min. For the disc-shaped test specimens removed from the screw tube after this vibration test, the percentage of active material layer loss was determined as the mass ratio [WB2 / WB1] of the specimen after vibration to the mass WB1 of the specimen before vibration. In this test, the closer the mass ratio [WB2 / WB1] is to 1, the stronger the bonding force between the solid particles constituting the active material layer, and an evaluation of "B" or higher is considered a passing level. - Evaluation Criteria - A: 0.99 ≤ [WB2 / WB1] ≤ 1.0 B: 0.95 ≤ [WB2 / WB1] < 0.99 C: [WB2 / WB1]<0.95
[0243] <Evaluation 3: Resistance Test> The battery resistance of each manufactured all-solid-state secondary battery was evaluated using the following method. Specifically, each of the manufactured solid-state secondary batteries (half-cells) No. C-1 to C-28 was charged at 25°C with a charging current of 0.1 mA until the battery voltage reached 3.6 V. Then, each solid-state secondary battery was initialized by discharging it with a discharge current of 0.1 mA until the battery voltage reached 1.9 V. Subsequently, as a rate test, the battery was charged at a charging current of 0.1 mA in a 25°C environment until the battery voltage reached 3.6 V, and then discharged at a discharge current of 0.1 mA until the battery voltage reached 1.9 V (Charge / Discharge Process (1)). After that, the battery was charged again at a charging current of 0.1 mA until the battery voltage reached 3.6 V, and then discharged at a discharge current of 1.5 mA until the battery voltage reached 1.9 V (Charge / Discharge Process (2)). After the charge-discharge processes (1) and (2) were completed, the discharge capacity was measured using the TOSCAT-3000 charge-discharge evaluation device (product name, manufactured by Toyo System Co., Ltd.). Using the measured discharge capacity, the discharge capacity retention rate (%) was calculated from the following formula, and the rate characteristics of the all-solid-state secondary battery were evaluated by applying it to the evaluation criteria below. In this test, a higher retention rate (%) indicates lower battery resistance (resistance of the positive electrode active material layer) of the all-solid-state secondary battery, and a score of "B" or higher is considered a passing level for this test. Maintenance rate (%) = [Discharge capacity of charge / discharge process (2) / Discharge capacity of charge / discharge process (1)] × 100 - Evaluation Criteria - A:90%≦Retention rate B:80%≦Retention rate<90% C: Retention rate <80%
[0244] [Table 3-1]
[0245] [Table 3-2]
[0246] The results shown in Tables 1 to 3 indicate the following: Comparative electrode compositions S-3 to S-10, S-24, and T-3, T-4, which do not contain polymer binders A and B that preferentially adsorb to the active material (AC) and inorganic solid electrolyte (SE), respectively, all fail to achieve a balance between the dispersion stability of the electrode composition, the binding of solid particles in the active material layer, and the battery resistance (resistance of the active material layer). Specifically, electrode compositions S-3 to S-7, S-9, and T-3, T-4 have poor dispersion stability. Furthermore, electrode composition S-8, which contains an excess of two types of polymer binders that do not correspond to polymer binders A and B, has excellent dispersion stability, but high battery resistance (resistance of the positive electrode active material layer). Positive electrode composition S-10, which contains particulate polymer binders, has poor dispersion stability, and positive electrode composition S-24 has poor dispersion stability and poor battery resistance. In contrast, electrode compositions S-1, S-2, S-11~S-23 and T-1, T-2, which contain polymer binders A and B in a dispersion medium (D) that preferentially adsorb to the active material (AC) and inorganic solid electrolyte (SE), respectively, all exhibit excellent dispersion stability, solid particle binding properties, and battery resistance, and can achieve a high level of balance among these three. [Explanation of Symbols]
[0247] 1 Negative electrode current collector 2 Negative electrode active material layer 3 Solid electrolyte layer 4 Cathode active material layer 5 Positive electrode current collector 6. Operating parts 10 All-solid-state secondary battery
Claims
1. An electrode composition comprising an inorganic solid electrolyte having conductivity of metal ions belonging to Group 1 or Group 2 of the periodic table, an active material, a polymer binder, and a dispersion medium, The polymer binder is A polymer binder A that dissolves in the dispersion medium, wherein the adsorption rate of the active material in the dispersion medium, measured by the following method, is 20% or more, and is greater than the adsorption rate of the inorganic solid electrolyte, measured by the following method; An electrode composition comprising polymer binder B, which dissolves in the dispersion medium, wherein the polymer binder B has an adsorption rate of 20% or more to the inorganic solid electrolyte in the dispersion medium according to the following measurement method, and is greater than the adsorption rate to the active material according to the following measurement method. <Method for measuring the adsorption rate (%) of the active material> Using the active material, polymer binder, and dispersion medium contained in the electrode composition, 1.6 g of the active material, 0.08 g of the polymer binder, and 8 g of the dispersion medium are stirred at 25°C for 30 minutes. After stirring, 2 g of the polymer binder is taken and allowed to dry. The mass BY of the dried polymer binder is measured, and the adsorption rate is calculated as the ratio of the mass adsorbed on the active material to the total mass of the polymer binder using the following formula AC. The average of the adsorption rates obtained by performing this measurement twice is taken as the adsorption rate (%) of the active material in the dispersion medium. Formula AC: Adsorption rate (%) = [(0.08-BY×8 / 2) / 0.08]×100 <Method for measuring the adsorption rate (%) of inorganic solid electrolytes> Using the inorganic solid electrolyte, polymer binder, and dispersion medium contained in the electrode composition, 0.5 g of the inorganic solid electrolyte, 0.26 g of the polymer binder, and 25 g of the dispersion medium are stirred at 25°C for 30 minutes. After stirring, 2 g of the polymer binder is taken and allowed to dry. The mass BX of the dried polymer binder is measured, and the adsorption rate is calculated as the ratio of the mass adsorbed on the inorganic solid electrolyte to the total mass of the polymer binder using the following formula SE. The average of the adsorption rates obtained by performing this measurement twice is taken as the adsorption rate (%) of the inorganic solid electrolyte in the dispersion medium. Formula SE: Adsorption rate (%) = [(0.26-BX×25 / 2) / 0.26]×100
2. The electrode composition according to claim 1, comprising a conductive additive.
3. The electrode composition according to claim 1, wherein the polymer forming at least one of polymer binder A and polymer binder B comprises a component having a functional group selected from the following functional group (a). <Functional group group (a)> Hydroxyl group, amino group, carboxyl group, sulfo group, phosphate group, phosphonic acid group, sulfanyl group, ether bond, imino group, amide bond, imide bond, urethane bond, urea bond, heterocyclic group, aryl group, carboxylic anhydride group
4. The electrode composition according to claim 1, wherein the polymer forming the polymer binder A has at least one of the following bonds in its main chain: urethane bond, urea bond, amide bond, imide bond, and ester bond.
5. The electrode composition according to claim 1, wherein the polymer forming the polymer binder B is obtained by polymerizing monomers having carbon-carbon unsaturated bonds.
6. The content of the polymer binder A is 1.5% by mass or less of the solid content of the electrode composition by 100% by mass. The electrode composition according to claim 1, wherein the content of the polymer binder B is 1.5% by mass or less of the solid content of the electrode composition by 100% by mass.
7. An electrode sheet for an all-solid-state secondary battery having an active material layer formed using the electrode composition described in any one of claims 1 to 6.
8. An all-solid-state secondary battery comprising a positive electrode active material layer, a solid electrolyte layer, and a negative electrode active material layer in this order, All-solid-state secondary battery, wherein at least one of the positive electrode active material layer and the negative electrode active material layer is an active material layer formed using the electrode composition described in any one of claims 1 to 6.
9. A method for producing an electrode composition according to any one of claims 1 to 6, A step of preparing an active material composition containing the active material, the polymer binder A, and the dispersion medium, A step of preparing a solid electrolyte composition containing the inorganic solid electrolyte, the polymer binder B, and the dispersion medium, A step of mixing the active material composition and the solid electrolyte composition, A method for producing an electrode composition having the following characteristics.
10. A method for manufacturing an electrode sheet for an all-solid-state secondary battery, comprising forming a film of the electrode composition described in any one of claims 1 to 6.
11. A method for manufacturing an all-solid-state secondary battery, comprising manufacturing an all-solid-state secondary battery via the manufacturing method described in claim 10.
Citation Information
Patent Citations
JP2015-244428A
Carboxymethyl cellulose or salt thereof, and electrode composition
WO2018062250A1
Inorganic solid electrolyte-containing composition, sheet for all-solid-state secondary batteries, electrode sheet for all-solid-state secondary batteries, all-solid-state secondary battery, method for producing sheet for all-solid-state secondary batteries and method for producing all-solid-state secondary battery
WO2021014852A1
Method for producing electrode composition, method for manufacturing electrode sheet for all-solid-state secondary battery, and method for manufacturing all-solid-state secondary battery
WO2021039948A1
Inorganic solid electrolyte-containing composition, sheet for all-solid-state secondary battery, and all-solid-state secondary battery, and method for manufacturing inorganic solid electrolyte-containing composition, sheet for all-solid-state secondary battery, and all-solid-state secondary battery
WO2021066060A1